Use of natural pozzolana in process for preparing cementitious composition
Combining natural pozzolans, slag, and accelerators with seawater or salt water forms cementitious mixtures that address the environmental impact of Portland cement by reducing emissions and improving material properties for construction applications.
Patent Information
- Application Number
- CN202380040227.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-21
- Filing Date
- 2023-12-21
- Publication Date
- 2024-12-27
AI Technical Summary
The cement industry contributes significantly to carbon dioxide emissions, and existing alternatives to Portland cement, such as natural pozzolans, face challenges like cracking, non-hydraulic performance, and incompatibility with metals, limiting their use in construction.
Formulations combining natural pozzolans, ground granulated blast furnace slag, and accelerators, optionally with aggregates and seawater or salt water, to create cementitious mixtures that solidify into artificial stone-like materials with negative carbon dioxide emissions, avoiding Portland cement.
These mixtures reduce greenhouse gas emissions, improve resistance to sulfate attack, and enhance suitability for marine uses, while providing a sustainable alternative to traditional cementitious materials.
Smart Images

Figure BDA0005131985090000162 
Figure BDA0005131985090000551 
Figure BDA0005131985090000561
Abstract
Description
Background Art
[0001] In 2015, global Portland cement manufacturing contributed approximately 2.8 billion metric tons of carbon dioxide, or CO2, emissions. These emissions are equivalent to 8% of the world's total CO2 emissions. The production of Portland clinker, which acts as a binder, is a key step in the manufacture of ordinary Portland cement (OPC). Limestone (CaCO3) is calcined at high temperatures in cement kilns to produce lime (CaO), resulting in the release of waste CO2.
[0002] These carbon dioxide reactions account for approximately 50% of the CO2 emissions produced, with 40% of emissions coming from burning fossil fuels to heat the kilns to the high temperatures required for this calcination process, and 10% of emissions coming from the fuels required to mine and transport the raw materials. Each ton of Portland cement produced contributes approximately one ton of CO2, directly through the heat of decomposition of calcium carbonate to produce lime and CO2, and indirectly through burning fossil fuels to heat the calcium carbonate in the kiln.
[0003] Over the past few decades, the cement industry has attempted to reduce emissions. The industry has implemented energy-efficient kilns, low-emission fuels, and increased clinker substitutes. However, these measures cannot meet the 24% cement emissions reduction required to limit global temperature rise to below 2°C (3.8°F) as stipulated in the Paris Agreement. Technologies such as carbon capture and storage (CSS) and "novel" cement have been explored to achieve this goal. Due to cost and energy consumption, CSS has not yet reached commercial scale development, and its implementation will be challenging. Therefore, alternative cement technologies provide the most reasonable way to reduce industry emissions. The present embodiments meet this need and other needs.
[0004] Although the use of natural pozzolans or volcanic ashes may be considered capable of being included in certain hydraulic binders, the use of natural pozzolans in particular formulations has not been appreciated. Previous attempts to use natural pozzolans or pozzolan cements without clinker have encountered a number of problems and other disadvantages, including, for example, difficulties in applications related to vertical and other structural construction contexts (e.g., cracking, non-hydraulic performance, inability to be used with steel and other metals, etc.). The present application is directed to various formulations comprising a combination of natural pozzolans and other materials to produce an alternative settable formulation to clinker-based cements such as Portland cement and / or other currently known mixtures (e.g., including mixtures that may contain natural pozzolans) that provide a reliable and sustainable alternative to the construction industry and other industries. Summary of the invention
[0005] The present application generally relates to alternative "cement" technologies (e.g., materials that solidify, harden, and / or adhere to other materials to bind them together, such as to make materials such as concrete), which include natural pozzolans or pozzolans with improved physical properties, including CO2 adsorption and the use of seawater or salt water derived from desalinated water of seawater or well water; waste products that reduce energy requirements, cost requirements, and environmental impact. According to some embodiments, certain formulations or mixtures are disclosed herein that are configured to be combined with water (and / or other liquids) to solidify and solidify to form materials suitable for construction. Such mixtures may include MgO or Mg(OH)2 and are alternatives to Portland cement, other calcium-containing binder materials, and other traditional binder formulations. In some embodiments, such mixtures do not contain Portland cement before being combined with water and / or other liquids (referred to herein as "dry" mixtures). As described herein, in some cases, mixtures that do not include Portland cement or any clinker can provide environmental benefits (e.g., by reducing greenhouse gas emissions).
[0006] In one aspect, provided herein is an artificial stonelike material that is set by pouring a cementitious mixture, the poured concrete mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) an aqueous solution comprising one or more accelerators.
[0007] In one aspect, provided herein is an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured concrete mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; (c) an aqueous solution comprising one or more accelerators, and (d) at least one aggregate.
[0008] In one aspect, the present invention provides an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured concrete mixture comprising: (a) pozzolan; (b) slag; (c) an aqueous solution, (d) one or more accelerators; and (e) optionally at least one aggregate.
[0009] In one aspect, provided herein is an artificial stone-like material formed from a cast cementitious mixture and configured to absorb and retain carbon dioxide, wherein the cast cementitious mixture comprises (a) natural pozzolan; (b) ground granulated blast furnace slag; (c) an aqueous solution comprising one or more accelerators; and (d) optionally at least one aggregate.
[0010] In one aspect, provided herein is a method for making an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing natural pozzolan with ground granulated blast furnace slag in an aqueous solution comprising one or more accelerators to form a cementitious mixture; (b) pouring the cementitious mixture into a structural component mold to form a cast cementitious mixture; and then (c) curing the cast cementitious mixture from step (b) in the structural mold to form an artificial stone-like material with negative carbon dioxide emissions.
[0011] In one aspect, provided herein is a method for making an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing pozzolan with one or more accelerators and MgO, Mg(OH)2 or other reactants and / or slag to form a dry cementitious mixture; (b) combining the dry cementitious mixture with an aqueous solution to form a cementitious mixture; and then (c) curing the cementitious mixture from step (b) to form an artificial stone-like material with negative carbon dioxide emissions.
[0012] In embodiments, the aqueous solution is seawater. In embodiments, the aqueous solution is non-drinking water. In embodiments, the aqueous solution is salt water. In embodiments, the aqueous solution is concentrated desalinated salt water. In embodiments, the aqueous mixture is water, such as well water. In embodiments, the well is a saltwater well. In embodiments, the aqueous solution is purified water. In embodiments, the salt water or seawater comprises a promoter. In embodiments, one or more additional promoters are added to the mixture (e.g., added to a dry mixture and / or aqueous solution), for example, assuming that the salt water or seawater does not contain the desired promoter. One benefit of the prior art includes direct use of salt water, such as without filtering, processing, evaporation or modification of salt water. Without being bound by theory, it is expected that other components of the salt water will not affect the performance of the mixture described herein. Therefore, another benefit of the prior art is that it does not require the use of fresh (e.g., drinking) water.
[0013] As used herein, reactants can come from any source. For example, Mg(OH)2 can come from any source. In embodiments, Mg(OH)2 comes from brucite.
[0014] In one aspect, provided herein is an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured concrete mixture comprising: (a) pozzolan; (b) slag; (c) one or more accelerators and (d) an aqueous solution. In an embodiment, the pozzolan is a natural pozzolan. In an embodiment, the pozzolan is an artificial pozzolan.
[0015] In one aspect, provided herein is an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured concrete mixture comprising: (a) pozzolan; (b) slag; (c) aqueous solution; (d) one or more accelerators; and (e) at least one aggregate.
[0016] In one aspect, provided herein is an artificial stone-like material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) slag; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate.
[0017] In one aspect, provided herein is a method of making an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing pozzolan in an aqueous solution with one or more accelerators and slag to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form an artificial stone-like material with negative carbon dioxide emissions. In an embodiment, the cementitious mixture is poured into a mold. In an embodiment, the cementitious mixture is poured into a structural component mold.
[0018] In one aspect, the present invention provides an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) MgO; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate.
[0019] In one aspect, the present invention provides an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) Mg(OH)2; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate.
[0020] In one aspect, there is provided herein an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan; (c) aqueous solution; and (d) one or more accelerators. In an embodiment, the poured cementitious mixture includes (e) at least one aggregate.
[0021] According to some embodiments, any one of the curable mixtures and formulations disclosed herein may include four different components. Curable mixtures or formulations may include (i) reactants, (ii) natural volcanic ash or volcanic ash, (iii) accelerators, and (iv) fillers and / or other additives. Such mixtures and formulations can be combined with water and / or other liquids and solidified, thereby producing a final cured product (e.g., structure, flat plate, etc.). According to some embodiments, the curable mixture or formulation may include reactants and natural volcanic ash and / or volcanic ash in equal or substantially equal proportions (by weight of the dry mixture). For any one of the mixtures or formulation embodiments disclosed herein, the ratios of reactants and natural volcanic ash and / or volcanic ash in formulations (e.g., dry formulations before adding any water and / or other liquids) may be relatively equal to each other. For example, the proportion of natural pozzolan and / or pozzolan in the dry mixture or formulation by weight percentage is 20% to 180% (e.g., 20%-180%, 30%-170%, 40%-160%, 50%-150%, 60%-140%, 70%-130%, 80%-120%, 90%-110%, 95%-105%, 98%-102%, 99%-101%, values between the foregoing ranges, etc.) of the proportion of the reactants in the dry mixture or formulation by weight percentage.
[0022] In one aspect, the present invention provides an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured concrete mixture comprising: (a) natural pozzolan or pozzolan (pozzolan); (b) reactants; and (c) an aqueous solution comprising one or more accelerators, and (d) at least one aggregate.
[0023] In one aspect, a curable mixture configured to solidify in the presence of water comprises reactants; a primary natural pozzolan or a pozzolan, wherein the proportion of the pozzolan by weight is 80% to 120% of the proportion of the reactants by weight of the mixture; and at least one accelerator, wherein the at least one accelerator comprises magnesium chloride in the form of MgCl2·6H2O or magnesium nitrate in the form of Mg(NO3)2·6H2O. DETAILED DESCRIPTION
[0024] An embodiment of the present invention provides an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan, such as ground granulated blast furnace slag; (c) an aqueous solution comprising one or more accelerators; (d) and optionally at least one aggregate. In addition, an embodiment of the present invention provides an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) slag, MgO or Mg(OH)2; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate. In addition, an embodiment of the present invention provides an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan; (c) MgO or Mg(OH)2; (d) an aqueous solution; (e) one or more accelerators; and (f) optionally at least one aggregate. In an embodiment, the poured cementitious mixture includes at least one aggregate.
[0025] Conventionally, concrete is a mixture of paste and aggregate or rock. The paste, composed of cementitious material and water, covers the surface of fine and coarse aggregate. Through a chemical reaction called hydration, the paste hardens and gains strength to form a rock-like substance called concrete. Concrete can be suitable for building skyscrapers, bridges, sidewalks and highways, houses and dams.
[0026] Cementitious materials for conventional forms of concrete include Portland cement. Portland cement is a fine powder made by heating limestone (CaCO3) and clay minerals in a kiln to form clinker (CaO), grinding the clinker, and adding 2%-3% gypsum. Several types of Portland cement are available, including ordinary Portland cement (OPC), which is gray, and white Portland cement. The low cost and widespread availability of limestone, shale, and other naturally occurring materials used in Portland cement made it one of the lowest cost materials widely used in the last century. However, it is one of the largest contributors to carbon dioxide emissions from the construction industry that contribute to climate change.
[0027] The manufacture of Portland cement can cause environmental impacts at all stages of the process. These include air pollution emissions in the form of dust, particulate emissions, gases; the release of carbon dioxide from raw materials during manufacture, and damage to the countryside caused by quarrying.
[0028] The present application relates to the unexpected benefits of using natural volcanic ash including basalt and / or volcanic ash as a substitute for other cement technologies. For example, natural volcanic ash avoids the problems associated with high-grade ore depletion and heating / smelting in land mining, but is derived from existing natural sources. In addition, the present application covers the combined use of natural volcanic ash and seawater or recycled waste brine to produce the covered cementitious products. Therefore, the use of natural volcanic ash from natural sources avoids the problem of obtaining a large amount of compounds required to produce cementitious products, thereby further offsetting carbon dioxide and energy requirements. In an embodiment, volcanic ash is used, such as artificial volcanic ash. In an embodiment, volcanic ash includes volcanic ash. In an embodiment, basalt is treated with acid before use. For example, basalt can be treated with acid to convert and separate minerals. In an embodiment, an inorganic acid is used. In an embodiment, the acid is hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, hydrofluoric acid, hydrobromic acid, perchloric acid or hydroiodic acid. In an embodiment, the acid is HCl. In an embodiment, basalt is not treated with acid.
[0029] Additional unexpected benefits of the technology described herein include: increased resistance to sulfate attack and improved suitability for marine uses and coral substrates. In addition, dry materials (e.g., volcanic ash, MgO, Mg(OH)2, slag and / or other components) can be added directly to seawater (e.g., seabed) as part of the hydration process. The technology described herein further reduces or substantially eliminates CO2 emissions when making and using Portland cement, while also removing CO2 from the atmosphere. I. definition
[0030] Before further describing the present invention, it should be understood that the present invention is not strictly limited to the specific embodiments described, and thus may, of course, vary. It should also be understood that the terminology used herein is for the purpose of describing specific embodiments only, and is not intended to be limiting, as the scope of the present invention will be limited only by the claims.
[0031] It must be noted that, unless the context clearly indicates otherwise, as used herein and in the appended claims, the singular forms "a / an" and "the" include plural references. It should be further understood that, as used herein, the term "a" entity or "an" entity refers to one or more of that entity. For example, a nucleic acid molecule refers to one or more nucleic acid molecules. Thus, the terms "a / n", "one or more", and "at least one" can be used interchangeably. Similarly, the terms "comprising", "including", and "having" can be used interchangeably.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described. All publications mentioned herein are incorporated herein by reference to disclose and describe methods and / or materials related to the cited publications. The publications discussed herein are provided only for their disclosures before the filing date of the present application. Anything herein should not be deemed to admit that the present invention is not entitled to be disclosed in advance due to previous inventions. In addition, the publication date provided may be different from the actual publication date, and the actual publication date may need to be independently confirmed.
[0033] It should be understood that, for the sake of clarity, certain features of the invention described in the context of separate embodiments may also be provided in combination in a single embodiment. Conversely, for the sake of brevity, various features of the invention described in the context of a single embodiment may also be provided individually or in any suitable subcombination. All combinations of the embodiments are specifically encompassed by the invention and disclosed herein, just as each combination is individually and explicitly disclosed. In addition, all subcombinations are also specifically encompassed by the invention and disclosed herein, just as each such subcombination is individually and explicitly disclosed herein.
[0034] It should be further noted that the claims may be drafted to exclude any optional elements. As such, this statement is intended to serve as antecedent basis for describing the elements of the associated claims using such exclusive terminology as "solely," "only," and the like, or using a "negative" limitation.
[0035] As used herein, the term "about" means a range of values including a stated value that one of ordinary skill in the art would consider to be reasonably similar to the stated value. In embodiments, about means within the standard deviation of a measurement generally accepted in the art. In embodiments, about means a range extending to + / - 10% of the stated value. In embodiments, about means the stated value.
[0036] As used herein, the term "accelerant" is used according to its common meaning and refers to a substance that improves chemical reactions and provides higher strength materials. In embodiments, the accelerants covered by the present application include, but are not limited to, sulfates, nitrates, phosphates, and chlorides. The amount of accelerant added may vary depending on various factors. For example, more accelerants may be added to a large amount of material (i.e., high quality). In addition, the lower the ambient temperature, the more accelerants can be used. The amount of accelerant used will vary according to the amount of volcanic ash, MgO, or Mg (OH) used. The amount of accelerant used will vary according to the ratio of volcanic ash, MgO, or Mg (OH) used. The amount of accelerant used will vary based on the aqueous solution used (e.g., water, non-drinking water, brackish water, brine, concentrated brine, seawater).
[0037] As used herein, the term "aggregates" or "aggregate" is used according to its ordinary meaning and refers to inert granular materials such as sand, gravel, lightweight aggregate or crushed stone (regardless of normal weight and / or lightweight), which are used in concrete together with cementitious materials and other optional raw materials (such as pigments and / or admixtures). In addition, as used herein, the term "aggregate" may include ASTM International C 33 fine aggregate, ASTM International C 33 coarse aggregate, and other granular materials mixed into the concrete mixture. Aggregates can be processed: crushed, screened, and washed to obtain appropriate cleanliness and gradation. In some cases, beneficiation processes such as winnowing or heavy media separation can be used to upgrade the quality. Once processed, the aggregates can be handled and stored to minimize segregation and degradation and prevent contamination, and also to protect from weathering and allow for drainage and / or evaporation of moisture. Aggregates from different sources or produced by different methods may differ significantly in particle shape, size, and texture. The shapes of the aggregates of the present disclosure may be cubic and reasonably regular, substantially rounded, angular, or irregular. The surface texture may range from relatively smooth with small exposed pores to irregular with small to large exposed pores. The particle shape and surface texture of both the fine and coarse aggregates may affect the proportioning of the mixture in terms of factors such as workability, pumpability, fine to coarse aggregate ratio, and water requirements.
[0038] As used herein, the term "brine" is used according to its common meaning and refers to a high concentration of salt in water. In embodiments, the concentration is in the range of about 3 g salt / liter of water to 26 g salt / liter of water. In embodiments, the salt concentration of the brine exceeds the salt concentration of natural seawater. In embodiments, the salt concentration of the brine is at least 101% of the salt concentration of natural seawater. In embodiments, the salt concentration of the brine is in the range of about 101% of the salt concentration of natural seawater to about 1000% of the salt concentration of natural seawater. In embodiments, brine is also referred to as desalinated brine effluent. In embodiments, brine may include but is not limited to trace metals, such as iron, nickel, chromium and molybdenum. In embodiments, brine is untreated. In embodiments, brine is minimally treated. In embodiments, brine is highly concentrated. In embodiments, brine contains one or more reactants. In embodiments, brine contains one or more reactants containing at least 75% (by weight). In embodiments, brine is supplemented with one or more reactants.
[0039] As used herein, the term "cement" is used according to its ordinary meaning and refers to a powdered substance prepared for making mortar or concrete. For example, cement can be a material that solidifies, hardens and / or adheres to other materials to make them bonded together, for example, to make materials such as concrete. In an embodiment, concrete is a mineral binder that does not contain any organic compounds. In an embodiment, the present application covers products that do not contain Portland cement. Some embodiments cover materials containing reduced Portland cement, which have less than 90%, 80%, 70%, 60%, 50%, 40%, 30%, 25%, 20%, 15%, 10% or 5% Portland cement; or any sub-value or sub-range between 0% and 90%. In an embodiment, Portland cement includes calcium, silicon, aluminum and iron. In an embodiment, Portland cement includes CaO, CaCO3, SiO2, Al2O3, Fe2O3 and CaSO4.H2O. In an embodiment, cement can be characterized as non-hydraulic cement or hydraulic cement. It should be further understood that "cementitious" can mean a material, including materials according to embodiments described herein, that has one or more characteristics or properties of cement. In some embodiments, the mixture does not include Portland cement.
[0040] As used herein, the term "concrete" is used in its ordinary sense and refers to an artificial stone-like material used for various structural purposes, made by mixing cement and various aggregates (such as sand, pebbles, gravel or shale) with water and allowing the mixture to harden. In embodiments, the term "stone-like" refers to a material that is visually, functionally and / or characteristically similar to stone, including when in its hardened state. In embodiments, "concrete substitute material" may be used interchangeably with "artificial stone-like material" throughout.
[0041] As used herein, the term "artificial stone-like material" refers to a cementitious material used for various structural purposes or non-structural purposes (such as slabs, panels, pavers or tiles), made by mixing a cement substitute as contemplated herein and various aggregates (such as sand, pebbles, gravel, lightweight aggregates or shale) with water and allowing the mixture to harden. In embodiments, the term "stone-like" refers to a material that visually resembles stone. In embodiments, "concrete replacement material" may be used interchangeably with "artificial stone-like material" throughout.
[0042] As used herein, the term "desalination" is used according to its ordinary meaning and refers to the process of removing salt or other minerals and contaminants from seawater, brackish water, well water, and wastewater effluents, and it is an increasingly common solution for obtaining fresh water for human consumption and for domestic / industrial use.
[0043] As used herein, the phrase "desalt wastewater" refers to the rejected brine from desalination. In embodiments, the process of removing salt from seawater to provide fresh water produces highly concentrated brine as a byproduct. The byproduct is typically disposed of by discharging it back into the ocean, a process that requires expensive pumping systems and must be carefully managed to prevent damage to marine ecosystems. If not properly managed, this process can introduce multi-component waste and increase temperatures, thereby disturbing local water and sediments. The process also endangers marine life due to residual chemicals from the pretreatment process being mixed into the brine.
[0044] As used herein, the term "fresh water" refers to water with a low concentration of dissolved salts. In embodiments, fresh water does not include seawater and brackish water. In embodiments, fresh water may include, but is not limited to, frozen water and meltwater in ice sheets, ice caps, glaciers, snowfields and icebergs, natural precipitation (e.g., rain, snow, hail, sleet). In embodiments, the salt concentration is less than 5%, less than 4%, less than 3%, less than 2%, and less than 1%, including subvalues therebetween.
[0045] As used herein, the term "non-hydraulic cement" is used according to its ordinary meaning and refers to a cement that does not set under wet conditions or under water. In embodiments, the non-hydraulic cement sets when it dries and reacts with CO2 in the air. In embodiments, the non-hydraulic cement resists degradation by chemicals after setting.
[0046] As used herein, the term "hydraulic cement" is used according to its ordinary meaning and refers to a cement that sets under moist conditions due to a chemical reaction between dry ingredients and water. In embodiments, the chemical reaction produces mineral hydrates that are completely or almost insoluble in water. In embodiments, hydraulic cement also refers to Portland cement.
[0047] As used herein, the term "mixing" is used according to its ordinary meaning and refers to any form of mixing and may include milling or grinding of substances in solid form.
[0048] As used herein, the term "mortar" is used according to its ordinary meaning and refers to a material composed of a binder.
[0049] As used herein, the term "negative CO2 emitting concrete replacement material" refers to a material that has a net positive CO2 absorption, as opposed to having a lower carbon footprint. In embodiments, the present application encompasses a material that generates carbon credits. In embodiments, the concrete replacement material absorbs more CO2 than it emits.
[0050] As used herein, the term "seawater" is used according to its ordinary meaning and refers to water from a sea or ocean. In embodiments, seawater includes various salts, dissolved inorganic (eg, minerals) and organic compounds, and other particulates.
[0051] As used herein, the term "silane" is used according to its ordinary meaning. In an embodiment, the silane is used as a coupling agent between two different materials, which produces a critical surface tension.
[0052] As used herein, the term "slag" is used according to its ordinary meaning and means any type of slag, and can be used interchangeably with "ground granulated blast furnace slag". Ground granulated blast furnace slag ("GGBFS") refers to a composition obtained by quenching molten iron slag (a byproduct of ironmaking and steelmaking) from a blast furnace in water or steam to produce a glassy granular product, which is then dried and ground into a fine powder. In an embodiment, slag includes any byproduct after the separation (e.g., by smelting) of a metal from its raw ore having a cementitious component and / or characteristic. In an embodiment, slag includes, but is not limited to, arc furnace slag, foundry furnace slag, induction furnace slag, and the like. In general, slag is a non-metallic byproduct comprising silicates, calcium aluminum silicates. Slag may include slag of any metal, such as, but not limited to, steel, iron, copper, nickel, lead, aluminum, and zinc. Without being bound by any one theory, the slags covered herein relate to use as a binder, which provides hydraulic properties. Hydraulic properties can in turn adjust the compressive strength of the material. As contemplated herein, the use of ground granulated blast furnace slag reduces iron waste disposal in landfills. In some embodiments, the slag meets ASTM requirements.
[0053] As used herein, the term "slurry" is used according to its ordinary meaning and refers to a mixture of relatively dense solids suspended in a liquid. In embodiments, "brine slurry" refers to desalinated water waste product.
[0054] As used herein, the term "structural element" means any vertical or horizontal load-bearing member of a structure that supports a dead or live load in addition to its own weight, and includes, but is not limited to, foundations, exterior or interior load-bearing walls, columns, post beams, floors, and roof structures.
[0055] As used herein, the term "mold" refers to any container or form used to impart shape to a material. In an embodiment, the mold comprises a hole. Volcanic ash
[0056] Without being bound by theory, the particle size of the volcanic ash can affect the reactivity of the material. For example, a smaller size can provide increased reactivity. The volcanic ash can be provided by any particle size. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #1200. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #1000. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #800. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #600. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #400. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #120 to about #325. In an embodiment, at least about 90% of the particles of the volcanic ash can pass through a mesh size of about #200 to about #1200. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #1000. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #800. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #700. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #600. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #500. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #400. In embodiments, at least about 90% of the particles of volcanic ash can pass through a mesh size of about #200 to about #325. The mesh size can be any value or sub-range within the specified range.
[0057] In embodiments, at least about 95% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 96% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 97% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 99% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #1000. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #800. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #600. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #400. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #120 to about #325. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #1200. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #1000. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #800. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #700. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #600. In embodiments, at least about 98% of the particles of volcanic ash can pass through a mesh size of about #200 to about #500. In embodiments, at least about 98% of the particles of the volcanic ash can pass through a mesh size of about #200 to about #400. In embodiments, at least about 98% of the particles of the volcanic ash can pass through a mesh size of about #200 to about #325. The mesh size can be any value or sub-range within the specified range. Natural volcanic ash
[0058] Natural pozzolans are raw pozzolans found in natural deposits. In embodiments, natural pozzolans are not calcined. A material is referred to as "calcined" when it has been heated below its melting temperature to change its composition or physical state.
[0059] Natural pozzolans have been used as a substitute for cement clinker in the production of Portland cement. Cement clinker is a solid material made by sintering limestone and aluminosilicate materials, which contains four mineral phases: two calcium silicates, alite (Ca3Si) and belite (Ca2Si), tricalcium aluminate (Ca3Al) and calcium aluminoferrite (Ca4AlFe). The clinker is ground into a fine powder and used as a binder, to which a small amount of gypsum must be added to avoid flash setting of tricalcium aluminate (Ca3Al2O6), the most reactive mineral phase in Portland clinker (exothermic hydrothermal reaction).
[0060] In contrast, the reactive chemical composition of volcanic ashes and natural volcanic ashes may include, but are not limited to, silicon dioxide (SiO2), aluminum oxide (Al2O3), and iron oxide (Fe2O3). Natural volcanic ashes encompass a variety of materials including, but not limited to, volcanic rocks (rhyolite, obsidian, pitchstone, pumice, basalt or trap rock, and andesite) tephra, sedimentary clays and shales, diatomaceous earth, and olivine.
[0061] Despite the advantages and historical use of natural pozzolans as clinker substitutes in the production of Portland cement-based concrete, several obstacles or disadvantages exist: The use of pozzolans may reduce the early strength of concrete, making such cements unsuitable for precast applications and potentially increasing construction time. It may also increase water demand during concrete production and may reduce carbonation resistance, thereby increasing the risk of corrosion of carbon (black) rebar. However, the materials and methods described herein provide an improved alternative.
[0062] In embodiments, the natural volcanic ash used in the compositions or methods provided herein is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay, shale, wollastonite, opal shale, diatomaceous earth, olivine, and combinations thereof. In embodiments, the natural volcanic ash comprises rhyolite. In embodiments, the natural volcanic ash comprises obsidian. In embodiments, the natural volcanic ash comprises pitchstone. In embodiments, the natural volcanic ash comprises pumice. In embodiments, the natural volcanic ash comprises basalt. In embodiments, the natural volcanic ash comprises andesite. In embodiments, the natural volcanic ash comprises volcanic ash. In embodiments, the natural volcanic ash comprises sedimentary clay. In embodiments, the natural volcanic ash comprises shale. In embodiments, the natural volcanic ash comprises wollastonite. In embodiments, the natural volcanic ash comprises diatomaceous earth. In embodiments, the natural volcanic ash comprises opal shale. In embodiments, the natural volcanic ash comprises olivine.
[0063] In embodiments, the natural pozzolans used in provided compositions or methods specifically exclude one or more of the natural pozzolans listed herein. Natural volcanic ash: volcanic rock
[0064] Rhyolite is a silica-rich volcanic rock with a fine-grained or glassy texture. It is formed from silica-rich magma that erupts from a volcanic vent and cools rapidly at the surface rather than slowly underground. The mineral composition of rhyolite includes quartz, sanidine, and plagioclase, with small amounts of amphibole and biotite. Chemically, the composition of rhyolite generally includes SiO2 and alkali metal oxides, such as K2O and Na2O.
[0065] Obsidian is also formed from lava that is ejected from volcanoes and cools quickly with minimal crystal growth (i.e., glassy or fine-grained). Similar to rhyolite, obsidian is extremely rich in SiO2, about 70 wt.% or more, and also includes MgO and Fe2O3. Although obsidian is used in manufacturing, its uses are typically for cutting and piercing tools.
[0066] Pitchstone is a volcanic glass similar to obsidian, formed when extruded lava cools rapidly. Pitchstone has a chemical composition similar to rhyolite and obsidian, with the amount of SiO2 ranging from about 70 wt.% to 75 wt.%. Pitchstone contains minerals such as quartz, alkali feldspar and plagioclase, as well as small amounts of pyroxene and hornblende.
[0067] Pumice is a porous volcanic rock that is produced when superheated, high-pressure rock is violently ejected from a volcano. Pumice typically has a porosity of about 64%-85% by volume. The mineral composition of pumice includes feldspar, pyroxene, hornblende, and zircon. Pumice contains primarily SiO2, Al2O3, and small amounts of other oxides such as FeO, Fe2O3, Na2O, and K2O.
[0068] Basalt is a fine-grained extrusive igneous rock formed by the rapid cooling of low-viscosity lava rich in magnesium and iron. Although basalt has a relatively low amount of SiO2 compared to other common igneous rocks, basalt generally has a composition of 45-52wt.% SiO2, 2-5wt.% total alkali metals, 0.5-2.0wt.% TiO2, 5-14wt.% and 14wt.% Al2O3. Basalt may contain other components, including but not limited to calcium oxide and / or magnesium oxide.
[0069] Andesite is a fine-grained volcanic rock formed by rapid cooling and solidification of lava from arc volcanoes or seepage fissures. Andesite contains sodium-rich plagioclase (Na,Ca)[(Si,Al)AlSi2]O8 and may contain (usually <20%) amphibole, biotite, pyroxene, and quartz minerals. In addition, andesite compositions include 52-63% silica and alkali metal oxide content (e.g., Na2O, KO) ranging from 0 to 7% w / w. When andesite compositions contain 52-57% or 57-63% SiO2, they are called low-silica or high-silica andesites, respectively.
[0070] Olivine is a magnesium iron silicate that is abundantly present as a dense material in the Earth's upper mantle. Olivine is chemically represented by (Mg,Fe)2SiO4. Generally speaking, olivine is abundant in low-silicon-dioxide mafic and ultramafic igneous rocks. Artificial volcanic ash
[0071] Other materials may have pozzolanic activity, including some man-made materials. In some embodiments, the compositions and methods described herein may utilize pozzolanic ash, including non-natural (e.g., man-made) pozzolanic ash. In embodiments, man-made pozzolanic ash is a calcined material. A material is referred to as "calcined" when it has been heated below the melting temperature to change its composition or physical state. In embodiments, man-made pozzolanic ash is a recycled material from industry (e.g., GGBFS).
[0072] Non-limiting examples of artificial pozzolans include metakaolin, fly ash (e.g., Class C fly ash), silica fume, ground glass (e.g., ground waste glass), slag (e.g., ground granulated blast furnace slag, blast furnace slag, steelmaking furnace slag, basic oxygen furnace slag, electric arc furnace slag, ladle slag, copper slag, steel slag, iron slag, lead slag, nickel slag, zinc slag, aluminum slag, slag of other metals, organic combustion residues (e.g., rice husk ash / rice hull ash), expanded clay, expanded shale and calcined clay, and combinations thereof.
[0073] In embodiments, the artificial pozzolan used in the provided compositions or methods comprises metakaolin. In embodiments, the artificial pozzolan comprises fly ash. In embodiments, the artificial pozzolan comprises silica ash. In embodiments, the artificial pozzolan comprises organic combustion residues. In embodiments, the artificial pozzolan comprises ground glass. In embodiments, the artificial pozzolan comprises ground waste glass. In embodiments, the artificial pozzolan comprises slag. In embodiments, the artificial pozzolan comprises ground granulated blast furnace slag. In embodiments, the artificial pozzolan comprises blast furnace slag. In embodiments, the artificial pozzolan comprises steelmaking furnace slag. In embodiments, the artificial pozzolan comprises basic oxygen furnace slag. In embodiments, the artificial pozzolan comprises electric arc furnace slag. In embodiments, the artificial pozzolan comprises ladle slag. In embodiments, the artificial pozzolan comprises copper slag. In embodiments, the artificial pozzolan comprises steel slag. In embodiments, the artificial pozzolan comprises iron slag. In embodiments, the artificial pozzolan comprises lead slag. In embodiments, the artificial pozzolan comprises nickel slag. In embodiments, the artificial pozzolan comprises zinc slag. In embodiments, the artificial pozzolan comprises aluminum slag. In an embodiment, the artificial pozzolan comprises slag of other metals. In an embodiment, the artificial pozzolan comprises organic combustion residues. In an embodiment, the artificial pozzolan comprises rice husk ash / rice hull ash. In an embodiment, the artificial pozzolan comprises expanded clay. In an embodiment, the artificial pozzolan comprises expanded shale. In an embodiment, the artificial pozzolan comprises calcined clay.
[0074] In embodiments, the materials described herein may be chemically treated (eg, with an acid) prior to use. In embodiments, the materials described herein are not chemically treated prior to use.
[0075] In embodiments, the artificial pozzolans used in provided compositions or methods specifically exclude one or more of the artificial pozzolans listed herein.
[0076] When the term "pozzolan" is stated, it is understood to mean natural pozzolan, artificial pozzolan or mixtures thereof. High efficiency water reducing agent
[0077] As covered herein, the use of alternative cements (such as natural pozzolans) generally increases water demand. Adding high-efficiency water reducers to concrete mixes can result in increased slump, lower water: cement (w / c) ratios, and / or reduced cement content required to obtain a given slump, either alone or in combination, thereby increasing the workability and strength of the concrete. These admixtures also improve the bond between concrete and steel, preventing cracking, isolation, honeycombing, and bleeding. Water reducer admixtures are also known as plasticizers and are classified into plasticizers, intermediate-effect plasticizers, and superplasticizers. Ordinary plasticizers reduce water demand by up to 10%. Intermediate-effect plasticizers reduce water demand by up to 15%. Superplasticizers reduce water demand by up to 30%. Common plasticizers include calcium lignin sulfonate, sodium lignin sulfonate, and ammonium lignin sulfonate. Superplasticizers include acrylic polymers based, poly(carboxylates), and poly(carboxylate ethers). In embodiments, plasticizers include but are not limited to calcium, sodium and ammonium lignin sulfonates, acrylic acid-based polymers, poly(carboxylates), poly(carboxylate ethers). In embodiments, depending on conditions, plasticizers may be used based on the chloride content of the cementitious mixture.
[0078] In embodiments, commercial proprietary admixtures of plasticizers include, but are not limited to, EUCON 1037, EUCON 37, EUCON 537, EUCON SP, EUCON SPJ, PLASTOL 341, PLASTOL 341S, PLASTOL 5000, PLASTOL 5000 / 5000SCC, PLASTOL 5700, PLASTOL 6400, PLASTOL 6200EXT, PLASTOL 3425, PLASTOL 3420, PLASTOL ULTRA 209, PLASTOL SPC from Euclid Chemical; SPMN and From Sika Chemical.
[0079] The high-range water reducer may result in a water reduction level of 12% to over 30% compared to a concrete mixture made without the addition of the high-range water reducer. In embodiments, the high-range water reducer may result in a water reduction level of up to 50%. In embodiments, the high-range water reducer may result in a water reduction level of over 0% to 50%, over 0% to 45%, over 0% to 40%, over 0% to 35%, over 0% to 30%, over 0% to 25%, over 0% to 20%, over 0% to 15%, over 0% to 10%, or over 0% to 5%. In embodiments, the high-range water reducer may result in a water reduction level of 5% to 50%, 10% to 50%, 15% to 50%, 20% to 50%, 25% to 50%, 30% to 50%, 35% to 50%, 40% to 50%, or 45% to 50%. In embodiments, the high-range water reducer may result in a water reduction level of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%. The percentages may be any value or sub-range within the recited ranges (including the endpoints).
[0080] The dosage rate of the high-efficiency water reducer is based on the cementitious material and composition and the chemical characteristics of the water reducer, and may be in the range of, but not limited to, 1 to 32 fluid ounces per 100 pounds of cementitious material or 65 to 2090 ml per 100 kg. In an embodiment, the dosage rate depends on the working conditions, such as the temperature, humidity of the environment, and the use of brine (i.e., recycled seawater), which includes a certain amount of chloride. Accelerating admixture
[0081] The use of quick-setting admixtures is contemplated herein. Quick-setting admixtures reduce the initial setting time of concrete and improve the strength of concrete by increasing the rate of hydration. These admixtures are used in situations where formwork needs to be removed early, emergency repairs are required, or construction is carried out in low-temperature areas. Examples of quick-setting admixtures include triethanolamine, calcium formate, silica fume, finely powdered silica gel, and calcium chloride. In an embodiment, quick-setting admixtures include but are not limited to triethanolamine, calcium formate, silica fume, finely powdered silica gel, and calcium chloride. In an embodiment, quick-setting admixtures include but are not limited to triethanolamine, calcium formate, finely powdered silica gel, and calcium chloride. In an embodiment, quick-setting admixtures do not include silica fume. Retarding admixture
[0082] The use of retarders is contemplated herein. Retarding admixtures slow the hydration rate of cement in its initial stages and increase the initial setting time of concrete. These admixtures are used in high temperature areas where concrete will solidify rapidly, which can lead to structural discontinuities and poor bonding between surfaces. In embodiments, retarders include, but are not limited to, citric acid, tartaric acid, glucose, lactose, maltose, cellobiose, sucrose, raffinose, phosphates, phosphonates, borates, lead oxide, zinc oxide, magnesium salts, fluorates, unrefined calcium, sodium, or ammonia. Some retarders may also serve as water reducers and are defined by ASTM as type D admixtures (i.e., water reducing and retarding). Such mixtures include lignin sulfonates, hydroxycarboxylic acids, and salts of hydroxycarboxylic acids.
[0083] The retarder may be applied at a dosage rate of 2-10 ounces per 100 pounds of cementitious material or 130-650 mL per 100 kg of cementitious material and is typically applied in the initial batch water of the concrete mix. In embodiments, the retarder may be applied at a dosage rate of 1-20 ounces per 100 pounds of cementitious material. In embodiments, the retarder may be applied at a dosage rate of 100-800 mL per 100 kg of cementitious material.
[0084] In embodiments, the retarder may be 1 ounce / 100 pounds of cementitious material, 1 ounce / 100 pounds of cementitious material, 2 ounces / 100 pounds of cementitious material, 3 ounces / 100 pounds of cementitious material, 4 ounces / 100 pounds of cementitious material, 5 ounces / 100 pounds of cementitious material, 6 ounces / 100 pounds of cementitious material, 7 ounces / 100 pounds of cementitious material, 8 ounces / 100 pounds of cementitious material, 9 ounces / 100 pounds of cementitious material, 10 ounces / 100 pounds of cementitious material, The dosage rate of cementitious material, 11 ounces / 100 pounds of cementitious material, 12 ounces / 100 pounds of cementitious material, 13 ounces / 100 pounds of cementitious material, 14 ounces / 100 pounds of cementitious material, 15 ounces / 100 pounds of cementitious material, 16 ounces / 100 pounds of cementitious material, 17 ounces / 100 pounds of cementitious material, 18 ounces / 100 pounds of cementitious material, 19 ounces / 100 pounds of cementitious material or 20 ounces / 100 pounds of cementitious material is applied. The amount of the dosage rate can be any value or sub-range within the recited range (including the endpoints).
[0085] In the embodiment, the retarder can be 100mL / 100kg cementitious material, 125mL / 100kg cementitious material, 150mL / 100kg cementitious material, 175mL / 100kg cementitious material, 200mL / 100kg cementitious material, 225mL / 100kg cementitious material, 250mL / 100kg cementitious material, 275mL / 100kg cementitious material, 300mL / 100kg cementitious material, 325mL / 100kg cementitious material, 350mL / 100kg cementitious material, 375mL / 100kg cementitious material, 400mL / 100kg cementitious material, 425mL / 100kg cementitious material, 450mL / 100kg cementitious material. The dosage rate of the cementitious material is preferably 475mL / 100kg, 500mL / 100kg, 525mL / 100kg, 550mL / 100kg, 575mL / 100kg, 600mL / 100kg, 625mL / 100kg, 650mL / 100kg, 675mL / 100kg, 700mL / 100kg, 725mL / 100kg, 750mL / 100kg, 775mL / 100kg, or 800mL / 100kg. The dosage rate may be any value or sub-range within the recited range (including the endpoints).
[0086] Surface retarder can be 100-300 feet 2 / gallon or 2.45m 2 / L-7.36m 2 / L coverage is used and is usually applied by spraying one or more thin, uniform coats on the top surface of the concrete. In an embodiment, the surface retarder can be applied 100 feet 2 / gallon, 110 feet 2 / gallon, 120 feet 2 / gallon, 130 feet 2 / gallon, 140 feet 2 / gallon, 150 feet 2 / Gallon, 160 feet 2 / gallon, 170 feet 2 / gallon, 180 feet 2 / Gallon, 190 feet 2 / gallon, 200 feet 2 / gallon, 210 feet 2 / gallon, 220 feet 2 / gallon, 230 feet 2 / gallon, 240 feet 2 / gallon, 250 feet 2 / gallon, 260 feet 2 / gallon, 270 feet 2 / gallon, 280 feet 2 / gallon, 290 feet 2 / gallon or 300 ft 2 The coverage rate can be any value or sub-range within the recited range (including the endpoints). Reactants
[0087] As used herein, the term "reactant" refers to one or more components of a cementitious mixture that provide reactivity to the mixture. Reactants include, for example, magnesium oxide, magnesium hydroxide, calcium carbonate, calcium oxide, calcium hydroxide, aluminum oxide, and aluminum hydroxide. In embodiments, the reactant includes magnesium oxide. In embodiments, the reactant includes magnesium hydroxide. In embodiments, the reactant includes calcium carbonate. In embodiments, the reactant includes calcium oxide. In embodiments, the reactant includes calcium hydroxide. In examples, the reactant includes aluminum hydroxide.
[0088] The reactants may be from any source. For example, the source of Mg(OH)2 may be brucite.
[0089] Without being bound by theory, the particle size of the reactant (or the source of the reactant) can affect the reactivity of the material. For example, a smaller particle size can provide improved reactivity. The reactant can be provided in any particle size. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #1200. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #1000. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #800. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #600. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #400. In an embodiment, at least about 90% of the particles of the reactant (or the source of the reactant) can pass through a mesh size of about #120 to about #325. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #1200. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #1000. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #800. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #700. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #600. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #500. In embodiments, at least about 90% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #400. In embodiments, at least about 90% of the particles of the reactant (or source of reactant) can pass through a mesh size of about #200 to about #325. The mesh size can be any value or sub-range within the specified range.
[0090] In embodiments, at least about 95% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 96% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 97% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 99% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1200. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #1000. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #800. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #600. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #400. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #120 to about #325. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #1200. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #1000. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #800. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #700. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #600. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #500. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #400. In embodiments, at least about 98% of the particles of the reactants (or sources of reactants) can pass through a mesh size of about #200 to about #325. The mesh size can be any value or sub-range within the specified range. II. Composition
[0091] In one aspect, embodiments of the present invention provide a material for use as, for example, cement and / or concrete material, the material comprising one or more of: volcanic ash; reactants or one or more promoters; and an aqueous solution. In embodiments, the present technology comprises a reactant (e.g., MgO, Mg(OH)2 or other reactants) in a ratio of about 1:1 with one or more volcanic ashes. In embodiments, the material comprises one or more of: natural volcanic ash; ground granulated blast furnace slag; reactants; aqueous solution; and one or more promoters. In embodiments, the material comprises one or more of: natural volcanic ash; ground granulated blast furnace slag; and an aqueous solution comprising one or more promoters. In embodiments, the material comprises one or more of: volcanic ash; MgO; aqueous solution; and one or more promoters. In embodiments, the material comprises one or more of: volcanic ash; Mg(OH)2; aqueous solution; and one or more promoters. In embodiments, the volcanic ash is natural volcanic ash. In embodiments, the volcanic ash is artificial volcanic ash. The material may further include, for example, at least one filler. The material may include at least one aggregate, such as sand, gravel, crushed stone, and combinations thereof. The promoter may include one or more nitrates, sulfates, sodium, chlorides, and potassium. The material can solidify after the components are mixed. Solidification can be accomplished by mixing and then pouring the mixture.
[0092] The materials described herein may be used in any suitable and desired manner, including any manner as described herein. For example, the materials may be used as or formed into building materials (including as described herein), such as structural foundations and slabs (e.g., by pouring into forms with or without reinforcement or support (e.g., rebar, etc.), porches, tiles (e.g., roofs, floors, walls, etc.), driveways and sidewalks, blocks, prefabricated walls or wall assemblies, rooms, etc., bricks, paving materials, articles such as lamp holders, furniture, frames, etc. In short, the materials may be used in any end use as described elsewhere herein.
[0093] In embodiments, the components of the cementitious mixture may be from any source. Different sources may have different levels of purity. Although sources with any purity level may be used, it should be understood that the purity level may affect the strength and / or curing time of the product.
[0094] In one aspect, embodiments of the present invention provide a material that solidifies by pouring a cementitious mixture, such as a cement and / or concrete replacement material, the poured cementitious mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) an aqueous solution comprising one or more accelerators. In one aspect, embodiments of the present invention provide a material that solidifies by pouring a cementitious mixture, such as a cement and / or concrete replacement material, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a material that solidifies by pouring a cementitious mixture, such as a cement and / or concrete replacement material, the poured cementitious mixture comprising: (a) pozzolan; (b) slag; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a material that solidifies by pouring a cementitious mixture, such as a cement and / or concrete replacement material, the poured cementitious mixture comprising: (a) pozzolan; (b) MgO; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a material that solidifies by pouring a cementitious mixture, such as a cement and / or concrete replacement material, the poured cementitious mixture comprising: (a) pozzolan; (b) Mg(OH)2; (c) an aqueous solution; and (d) one or more accelerators.
[0095] In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) an aqueous solution comprising one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) slag; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) MgO; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) Mg(OH)2; (c) aqueous solution; and (d) one or more accelerators. In one aspect, the curable mixture configured to solidify in the presence of water comprises reactants, primary natural pozzolans or pozzolans, wherein the weight proportion of the pozzolans is 80% to 120% of the weight proportion of the reactants in the mixture, and at least one accelerator, wherein the at least one accelerator comprises magnesium chloride in the form of MgCl2·6H2O or magnesium nitrate in the form of Mg(NO3)2·6H2O.
[0096] In embodiments, the accelerator comprises one or more of nitrates, sulfates, sodium, chlorides, and phosphates. In embodiments, the accelerator comprises nitrates. In embodiments, the accelerator comprises sulfates. In embodiments, the accelerator comprises sodium. In embodiments, the accelerator comprises chlorides. In embodiments, the accelerator comprises phosphates. In embodiments, when the mixture is prepared on a large scale, adding larger amounts of sulfates mitigates heat generation without negatively affecting the strength of the final material.
[0097] In an embodiment, the quick-setting admixture is selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride. In an embodiment, the quick-setting admixture includes triethanolamine. In an embodiment, the quick-setting admixture includes calcium formate. In an embodiment, the quick-setting admixture includes silica fume. In an embodiment, the quick-setting admixture includes finely powdered silica gel. In an embodiment, the quick-setting admixture includes calcium chloride.
[0098] In embodiments, the promoter is added to the aqueous solution prior to addition to the volcanic ash, slag, MgO and / or Mg(OH) 2. In embodiments, the promoter is combined with one or more of the volcanic ash, slag, MgO and / or Mg(OH) 2 prior to addition to the aqueous solution.
[0099] In embodiments, the poured cementitious mixture further comprises at least one aggregate. In embodiments, at least one aggregate is selected from sand, gravel, lightweight aggregate, crushed stone, and combinations thereof. In embodiments, at least one aggregate comprises sand. In embodiments, at least one aggregate comprises gravel. In embodiments, at least one aggregate comprises lightweight aggregate. In embodiments, at least one aggregate comprises crushed stone. In embodiments, at least one aggregate comprises untreated (e.g., unground) slag. In embodiments, at least one aggregate comprises untreated (e.g., unground) glass (e.g., waste glass). The aggregate may be of any size.
[0100] In embodiments, the average particle size of the aggregate is from about 0.01 mm to about 12 mm. In embodiments, the average particle size of the aggregate is from about 0.01 mm to about 3 mm. In embodiments, the average particle size of the aggregate is from about 3 mm to about 8 mm. In embodiments, the average particle size of the aggregate is from about 8 mm to about 12 mm.
[0101] In an embodiment, the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay, sedimentary shale, calcined clay, rice husk ash, diatomaceous earth, metakaolin, olivine, and combinations thereof. In an embodiment, the natural volcanic ash is basalt.
[0102] In one aspect, embodiments of the present invention provide a concrete replacement material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) an aqueous solution comprising one or more accelerators. In one aspect, embodiments of the present invention provide a concrete replacement material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) artificial pozzolan; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a concrete replacement material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) slag; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a concrete replacement material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) MgO; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide a concrete replacement material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) Mg(OH)2; (c) an aqueous solution; and (d) one or more accelerators.
[0103] In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) an aqueous solution comprising one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) natural pozzolan; (b) ground granulated blast furnace slag; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) slag; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, embodiments of the present invention provide an artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) MgO; (c) an aqueous solution; and (d) one or more accelerators. In one aspect, an embodiment of the present invention provides an artificial stone-like material that is solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) pozzolan; (b) Mg(OH)2; (c) an aqueous solution; and (d) one or more accelerators.
[0104] In an embodiment, the cementitious mixture includes MgO and / or Mg(OH)2. In an embodiment, the cementitious mixture includes MgO. In an embodiment, the cementitious mixture includes Mg(OH)2. In an embodiment, the cementitious mixture includes MgO and Mg(OH)2. In an embodiment, the ratio of MgO to Mg(OH)2 in the cementitious mixture is 4:1 to 1:4. Any ratio of MgO to Mg(OH)2 within this range can be used, for example 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, or any value or sub-range therebetween.
[0105] In embodiments, the slag included in the mixture may be replaced (or supplemented) by one or more other pozzolans, such as, for example and without limitation, Class C fly ash and / or any other material comprising similar cementitious properties capable of being combined with the reactant (e.g., magnesium oxide). According to some embodiments, a component of the dry mixture disclosed herein comprises a primary cementitious component. In some configurations, the primary cementitious component comprises a pozzolan. In other embodiments, the primary cementitious component comprises a pozzolan, and / or other cementitious components configured to be combined with the magnesium oxide of the mixture so that the components self-form a binder in the presence of water or other liquids. According to some embodiments, any primary cementitious component meets all or at least some of the requirements specified in ASTM C618.
[0106] In an embodiment, the concrete replacement material is set by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
[0107] In an embodiment, the artificial stone-like material is set by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
[0108] In an embodiment, the ratio of reactants (MgO and / or Mg(OH)2) to pozzolans (natural and / or artificial pozzolans) in the cementitious mixture is about 1:5 to about 5:1 in wt.%. Any ratio of reactants to pozzolans within this range may be used, for example, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or any value or sub-range therebetween. In an embodiment, the ratio of reactants (MgO and / or Mg(OH)2) to pozzolans (natural and / or artificial pozzolans) in the cementitious mixture is about 1:1.
[0109] In an embodiment, the ratio of artificial pozzolan to natural pozzolan in the cementitious mixture is from about 1:5 to about 5: 1 on a wt.% basis. Any ratio of artificial pozzolan to natural pozzolan within this range can be used, for example, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or any value or sub-range therebetween.
[0110] In embodiments, the combined amount of reactants and pozzolans in the dry cementitious mixture (before adding the aqueous solution) is about 10 to about 40 wt.%. In embodiments, the combined amount of reactants and pozzolans in the dry cementitious mixture (before adding the aqueous solution) is about 10 to about 30 wt.%. In embodiments, the combined amount of reactants and pozzolans in the dry cementitious mixture (before adding the aqueous solution) is about 10 to about 20 wt.%. In embodiments, the combined amount of reactants and pozzolans in the dry cementitious mixture (before adding the aqueous solution) is about 15 to about 30 wt.%. In embodiments, the combined amount of reactants and pozzolans in the dry cementitious mixture (before adding the aqueous solution) is about 15 to about 20 wt.%.
[0111] In some embodiments, the proportions of reactants and volcanic ash in the formulation (e.g., a dry formulation before adding any water and / or any other liquid) are relatively equal to each other. For example, the weight percent ratio of volcanic ash in the dry mixture or formulation is 80% to 120% (e.g., 80%-120%, 90%-110%, 95%-105%, 98%-102%, 80%-100%, 85%-100%, 90%-100%, 95%-100%, 80%-90%, 85%-95%, 100%-120%, 100%-115%, 100%-110%, 100%-105%, 105%-115%, 105%-120%, values between the foregoing ranges, etc.) of the weight percent ratio of the reactants in the dry mixture or formulation. In other embodiments, the weight percent ratio of the pozzolan in the dry mixture or formulation is 70% to 130% of the weight percent ratio of the reactants in the dry mixture or formulation (e.g., 70%-130%, 70%-120%, 80%-130%, 80%-120%, 90%-110%, 95%-105%, 98%-102%, 70%-100%, 80%-100%, 85%-100%, 90%-100%, 95%-100%, 80%-90%, 85%-95%, 100%-120%, 100%-115%, 100%-110%, 100%-105%, 105%-115%, 105%-120%, values in between the foregoing ranges, etc.).
[0112] According to some embodiments, the formulation or mixture comprises a combined reactant and pozzolan content, which is 40% to 80%, for example 40% to 70% (e.g., 40%-70%, 50%-60%, 40%-60%, 40%-50%, 40%-45%, 45%-50%, 45%-55%, 45%-60%, 45%-65%, 45%-70%, 50%-55%, 50%-65%, 50%-70%, 55%-60%, 55%-65%, 55%-70%, 60%-65%, 60%-70%, any percentages in between the foregoing ranges, etc.) by weight of the dry formulation or mixture. In certain configurations, the combined ratio of reactants and volcanic ash in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is at least 40% (e.g., at least 40%, 45%, 50%, 55%, 60%, 65%, higher than 65%, etc.) as needed or required. In certain embodiments, the combined ratio of reactants and volcanic ash in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is at least 15% (e.g., at least 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, higher than 65%, etc.) as needed or required.
[0113] According to some embodiments, the formulation or mixture comprises a combined reactant and pozzolan content that is between 15% and 50% by weight of the dry formulation or mixture (e.g., 15%-50%, 20%-40%, 25%-35%, 15%-20%, 15%-25%, 15%-30%, 15%-35%, 15%-40%, 15%-45%, 20%-25%, 20%-30%, 20%-35%, 20%-40%, 20%-45%, 20%-50%, 25%-30%, 25%-40%, 25%-50%, 30%-35%, 30%-40%, 30%-50%, other percentages between the foregoing ranges, etc.).
[0114] In some embodiments, the formulation or mixture comprises a reactant content, which is between 20% and 50% by weight of the dry formulation or mixture (e.g., 20%-50%, 20%-45%, 20%-40%, 20%-25%, 20%-30%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-30%, 25%-35%, 25%-40%, 30%-50%, 30%-45%, 30%-35%, 30%-40%, 22%-28%, 23%-27%, other percentages between the foregoing ranges, etc.). In certain configurations, the proportion of reactants in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is less than 40% (e.g., less than 40%, 39%, 38%, 37%, 36%, 35%, 34%, 33%, 32%, 31%, 30%, 25%, or less than 20%, 25%-30%, 20%-25%, 10%-20%, 5%-10%, 5%-15%, a specific percentage between the above values, etc.). In some embodiments, the proportion of reactants in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is less than 10% (e.g., less than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, a specific percentage between the above values, etc.).
[0115] According to some configurations, the proportion of reactants in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is 20% to 35% by weight of the dry mixture (e.g., 20%-35%, 20%-30%, 20%-25%, 22%-28%, 25%-30%, 25%-35%, 30%-35%, values between the above ranges, etc.). Similarly, in some configurations, the proportion of volcanic ash in the dry mixture is 20% to 35% by weight of the dry mixture (e.g., 20%-35%, 20%-30%, 20%-25%, 22%-28%, 25%-30%, 25%-35%, 30%-35%, values between the above ranges, etc.).
[0116] According to some configurations, the proportion of reactants in the dry mixture (e.g., before the mixture is combined with water and / or other liquids) is 5% to 20% by weight of the dry mixture (e.g., 5%-20%, 5%-15%, 5%-10%, 10%-20%, 10%-15%, values between the above ranges, etc.). Similarly, in some configurations, the proportion of volcanic ash in the dry mixture is 5% to 20% by weight of the dry mixture (e.g., 5%-20%, 5%-15%, 5%-10%, 10%-20%, 10%-15%, values between the above ranges, etc.).
[0117] In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 75:25wt.% to 25:75wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 65:35wt.% to 35:65wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 60:40wt.% to 40:60wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is about 50:50wt.%. The ratio can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0118] In embodiments, the ratio of volcanic ash to slag is 75:25wt.% to 25:75wt.%. In embodiments, the ratio of volcanic ash to slag is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of volcanic ash to slag is 65:35wt.% to 35:65wt.%. In embodiments, the ratio of volcanic ash to slag is 60:40wt.% to 40:60wt.%. In embodiments, the ratio of volcanic ash to slag is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of volcanic ash to slag is about 50:50wt.%. The ratio can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0119] In embodiments, the ratio of reactants to volcanic ash is 4:1 to 1:4 wt.%. In embodiments, the ratio of reactants to volcanic ash is 3.5:1 to 1:3.5 wt.%. In embodiments, the ratio of reactants to volcanic ash is 3:1 to 1:3 wt.%. In embodiments, the ratio of reactants to volcanic ash is 2.5:1 to 1:2.5 wt.%. In embodiments, the ratio of reactants to volcanic ash is 2:1 to 1:2 wt.%. In embodiments, the ratio of reactants to volcanic ash is 1.1:1 to 1:1.1 wt.%. The ratio may be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0120] In embodiments, at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof. In embodiments, at least one aggregate is non-reactive slag or crushed non-reactive slag.
[0121] In some embodiments, the cementitious mixture does not include, and may specifically exclude, MgO obtained from a calcination reaction. In some embodiments, the cementitious mixture includes MgO, wherein less than 90%, 80%, 70%, 60%, 50%, 40%, 30%, 25%, 20%, 15%, 10%, or 5% of the MgO is obtained from a calcination reaction; or any subvalue or subrange between 0% and 90%.
[0122] In embodiments, the amount of natural pozzolan is in the range of about 33 wt.% to about 300 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 50 wt.% to about 200 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present is in the range of about 85 wt.% to about 115 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 90 wt.% to about 110 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 151 wt.%, 152 wt.%, 153 wt.%, 154 wt.%, 155 wt.%, 156 wt.%, 157 wt.%, 158 wt.%, 159 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 169 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 %, 165wt.%, 170wt.%, 175wt.%, 180wt.%, 185, 190wt.%, 195wt.%, 200wt.%, 205wt.%, 210wt.%, 215wt.%, 220wt.%, 230wt.%, 235wt.%, 240wt.%, 245wt.%, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0123] In embodiments, the amount of natural pozzolan relative to the amount of artificial pozzolan can be included in the mixture in any proportion. In embodiments, the amount of natural pozzolan relative to the amount of artificial pozzolan ranges from about 33 wt.% to about 300 wt.%. In some embodiments, the amount of natural pozzolan present is within the range of about 50 wt.% to about 200 wt.% relative to the amount of artificial pozzolan. In embodiments, the amount of natural pozzolan present is within the range of about 85 wt.% to about 115 wt.% relative to the amount of artificial pozzolan. In some embodiments, the amount of natural pozzolan present is within the range of about 90 wt.% to about 110 wt.% relative to the amount of artificial pozzolan. In embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 wt.%, 182 %, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0124] In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 12 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 15 wt.% to about 30 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present relative to the amount of pozzolan (e.g., ground granulated blast furnace slag) is about 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, or 30 wt.%. This amount can be any subvalue or subrange therebetween, inclusive, and includes, but is not limited to, those specifically noted herein.
[0125] In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of reactants. In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 12 wt.% relative to the amount of reactants. In embodiments, the amount of nitrate present is in the range of about 15 wt.% to about 30 wt.% relative to the amount of reactants. In embodiments, the amount of nitrate present relative to the amount of reactants is about 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, or 30 wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0126] In embodiments, the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 110 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 50 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 80 wt.% to about 110 wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present relative to the amount of pozzolan (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, %. .%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, 60wt.%, 70wt.%, 80wt.%, 90wt.%, 100wt.%, 110wt.%; or its sub-integer, including the range between the endpoints. For example, in an embodiment, the amount of sulfate present is 31wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). In other embodiments, the amount of sulfate present is 90wt.% relative to the amount of volcanic ash (e.g., ground granulated blast furnace slag). The amount can be any sub-value or sub-range therebetween, including the endpoints, and includes but is not limited to those specifically indicated herein.
[0127] In embodiments, the amount of sulfate present relative to the amount of reactants ranges from about 0.1 wt.% to about 90 wt.%. In embodiments, the amount of sulfate present relative to the amount of reactants ranges from about 20 wt.% to about 110 wt.%. In embodiments, the amount of sulfate present relative to the amount of reactants ranges from about 20 wt.% to about 50 wt.%. In embodiments, the amount of sulfate present relative to the amount of reactants ranges from about 80 wt.% to about 110 wt.%. In embodiments, the amount of sulfate present relative to the amount of reactants is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%. %. .%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, 60wt.%, 70wt.%, 80wt.%, 90wt.%, 100wt.%, 110wt.%; or its sub-integer, including the range between the endpoints. For example, in embodiments, the amount of sulfate present is 31wt.% relative to the amount of reactants. In other embodiments, the amount of sulfate present is 90wt.% relative to the amount of reactants. The amount can be any sub-value or sub-range therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0128] In embodiments, the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of chloride depends on the end use and the size of the batch. Without being bound by any one theory, the use of chloride contributes to the density of the batch. In embodiments, the amount of chloride present relative to the amount of pozzolan (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt%; or a sub-integer thereof. For example, in embodiments, the amount of chloride present relative to the amount of pozzolan (eg, ground granulated blast furnace slag) is 1.8 wt.%. This amount can be any subvalue or subrange therebetween, including endpoints, and including but not limited to those specifically noted herein.
[0129] In embodiments, the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of reactants. In embodiments, the amount of chloride depends on the end use and the size of the batch. In embodiments, the amount of chloride present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt%; or a sub-integer thereof. For example, in embodiments, the amount of chloride present is 1.8 wt.% relative to the amount of reactants. This amount can be any subvalue or subrange therebetween, inclusive of the endpoints, and including, but not limited to, those specifically noted herein.
[0130] In embodiments, the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of phosphate present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.%, 2.5 wt.%, 2.6 wt.%, 2.7 wt.%, 2.8 wt.%, 2.9 wt.%, 3.0 wt.%, 3.1 wt.%, 3.2 wt.%, 3.3 wt.%, 3.4 wt.%, 3.5 wt.%, 3.6 wt.%, 3.7 wt.%, 3.8 wt.%, 3.9 wt.%, 4.1 wt.%, 4.2 wt.%, 4.3 wt.%, 4.4 wt.%, 4.5 wt.%, 4.6 wt.%, 4.7 wt.%, 4.8 wt.%, 4.9 wt.%, 4.1 %, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%; or its sub-integer. This amount can be any sub-value or sub-range therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0131] In embodiments, the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of reactants. In embodiments, the amount of phosphate present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 %, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%; or a sub-integer thereof. The amount can be any sub-value or sub-range therebetween, including endpoints, and including but not limited to those specifically indicated herein.
[0132] Other "low-carbon" concretes inject CO2 gas into their mix, then cure to capture the CO2. However, this does not result in the capture of large amounts of carbon from the atmosphere, and the CO2 must be captured by an industrial process, which may not be feasible. In contrast, the concrete replacement material described herein removes CO2 from the air via a chemical reaction that occurs at room temperature. The reaction permanently mineralizes the CO2 in the concrete replacement material.
[0133] In embodiments, CO2 is captured in a concrete substitute material or an artificial stone-like material. In embodiments, CO2 is crystallized in a concrete substitute material or an artificial stone-like material. In embodiments, the retention of CO2 in a material results in an increase in the strength of the material. In embodiments, a concrete substitute material absorbs and retains at least 0.04kg CO2 / kg concrete substitute material. In embodiments, a concrete substitute material absorbs and retains about 0.04kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, a concrete substitute material absorbs and retains about 0.04kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, a concrete substitute material absorbs and retains about 0.05kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, a concrete substitute material absorbs and retains about 0.07kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, a concrete substitute material absorbs and retains about 0.08kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, a concrete substitute material absorbs and retains about 0.09kg to about 1kg CO2 / kg concrete substitute material per year. In embodiments, the concrete replacement material absorbs and retains about 0.04 kg to about 0.9 kg CO2 / kg concrete replacement material per year. In embodiments, the concrete replacement material absorbs and retains about 0.04 kg to about 0.8 kg CO2 / kg concrete replacement material per year. In embodiments, the concrete replacement material absorbs and retains about 0.04 kg to about 0.7 kg CO2 / kg concrete replacement material per year. In embodiments, the concrete replacement material absorbs and retains about 0.09 kg to about 0.7 kg CO2 / kg concrete replacement material per year.
[0134] In embodiments, the artificial stone-like material absorbs and retains at least 0.04kg CO2 / kg artificial stone-like material. In embodiments, the artificial stone-like material absorbs and retains about 0.04kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.04kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.05kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.07kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.08kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.09kg to about 1kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.04kg to about 0.9kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.04 kg to about 0.8 kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.04 kg to about 0.7 kg CO2 / kg artificial stone-like material per year. In embodiments, the artificial stone-like material absorbs and retains about 0.09 kg to about 0.7 kg CO2 / kg artificial stone-like material per year.
[0135] In an embodiment, the concrete replacement material absorbs CO2 and retains at least 5-52% by weight of the concrete replacement material over a 15 year period.
[0136] In an embodiment, the artificial stone-like material absorbs CO2 and retains at least 5-52% by weight of the artificial stone-like material over a period of 15 years.
[0137] In another aspect, embodiments of the present invention provide a concrete replacement material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) natural pozzolan; (b) ground granulated blast furnace slag; and (c) optionally at least one aggregate. In another aspect, embodiments of the present invention provide a concrete replacement material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) slag; and (c) optionally at least one aggregate. In another aspect, embodiments of the present invention provide a concrete replacement material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) MgO; and (c) optionally at least one aggregate. In another aspect, embodiments of the present invention provide a concrete replacement material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) Mg(OH)2; and (c) optionally at least one aggregate.
[0138] In another aspect, embodiments of the present invention provide an artificial stone-like material formed from a cast cementitious mixture and configured to absorb and retain carbon dioxide, the cast cementitious mixture comprising (a) natural pozzolan; (b) ground granulated blast furnace slag; (c) an aqueous solution comprising one or more promoters; and (d) optionally at least one aggregate. In another aspect, embodiments of the present invention provide an artificial stone-like material formed from a cast cementitious mixture and configured to absorb and retain carbon dioxide, the cast cementitious mixture comprising (a) natural pozzolan; (b) ground granulated blast furnace slag; (c) an aqueous solution; (d) one or more promoters; and (e) optionally at least one aggregate. In another aspect, embodiments of the present invention provide an artificial stone-like material formed from a cast cementitious mixture and configured to absorb and retain carbon dioxide, the cast cementitious mixture comprising (a) pozzolan; (b) slag; (c) an aqueous solution, (d) one or more promoters; and (e) optionally at least one aggregate. In another aspect, embodiments of the present invention provide an artificial stone-like material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) MgO; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate. In another aspect, embodiments of the present invention provide an artificial stone-like material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising (a) pozzolan; (b) Mg(OH)2; (c) an aqueous solution; (d) one or more accelerators; and (e) optionally at least one aggregate.
[0139] In embodiments, the poured cementitious mixture absorbs and retains carbon dioxide for a period of time as it cures and hardens.
[0140] In embodiments, the poured cementitious mixture absorbs CO2 and retains at least 5-52% by weight of the material over a 15 year period.
[0141] In embodiments, the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
[0142] In embodiments, the ratio of volcanic ash (e.g., natural volcanic ash, artificial volcanic ash, or both) by weight is 80% to 120% of the ratio of reactants by weight of the mixture. In embodiments, the ratio of volcanic ash (e.g., natural volcanic ash, artificial volcanic ash, or both) by weight is 5:1 to 1:5 of the ratio of reactants by weight of the mixture. In embodiments, the sum of the ratios of reactants and volcanic ash comprises at least 12% by weight of the mixture. In embodiments, the mixture does not include clinker or portland cement or gypsum. In some embodiments, the mixture does not include gypsum as an initial mixture component. For example, in some embodiments, although the dry mixture does not include gypsum, gypsum in a final or intermediate form may be produced after the dry mixture is combined with water (e.g., during post-curing).
[0143] In embodiments, the mixtures or formulations disclosed herein are configured to produce a final cured product that, once combined with water and / or one or more other liquids and given sufficient time to solidify, is suitable for long-term contact with reinforcing steel (rebar), mesh, other types of steel (beams, channels, rods, fasteners, etc.), and / or any other metal or corrosive material. Thus, such formulations can be widely used in the construction industry where steel or other metal reinforcement and / or contact is desired or required. However, in other embodiments, as further discussed herein, the formulations can be used in structural or non-structural applications, regardless of whether the rebar or other metal contacts the final cured product produced by such formulations.
[0144] In embodiments, once combined with water and allowed to cure, the mixture has a 28-day strength of at least 2000 psi (e.g., at least 2000, 2100, 2200, 2300, 2400, 2500, 3000-3500, 3500-4000 psi, greater than 4000 psi, etc.). In embodiments, once combined with water and allowed to cure, the mixture has a 1-day strength of at least 400 psi (e.g., 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2000-2500, 2500-3000, greater than 3000 psi, etc.). In one aspect, once combined with water and allowed to cure, the mixture has a 1-day strength of at least 600 psi. In some aspects, once combined with water and cured, the mixture has a 1-day strength of at least 1000 psi. In some configurations, once combined with water and cured, the mixture has a 1-day strength of at least 1000 psi (e.g., 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2500, 3000, 3500, 4000, 4500 psi, greater than 4500 psi, etc.). In some aspects, once combined with water and cured, the mixture has a 7-day strength of at least 3000 psi. In some aspects, once combined with water and allowed to cure, the mixture has a 7-day strength of at least 2000 psi (e.g., 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600, 3700, 3800, 3900, 4000, 4500, 5000, 5500 psi, greater than 5500 psi, etc.).
[0145] In one aspect, the cementitious mixture includes reactants comprising one or both of magnesium oxide and / or magnesium hydroxide. In one aspect, the cementitious mixture includes reactants comprising one or more of magnesium oxide and / or magnesium hydroxide and / or calcium carbonate and / or calcium oxide and / or calcium hydroxide and / or aluminum oxide and / or aluminum hydroxide. In embodiments, the reactants include magnesium oxide. In embodiments, the reactants include magnesium hydroxide. In embodiments, the reactants include calcium carbonate. In embodiments, the reactants include calcium oxide. In embodiments, the reactants include calcium hydroxide. In embodiments, the reactants include aluminum oxide. In embodiments, the reactants include aluminum hydroxide.
[0146] In one aspect, cementitious mixture comprises two or more reactants. In one aspect, cementitious mixture comprises three or more reactants. In embodiments, reactants may be present in, but not limited to, natural volcanic ash and / or volcanic ash (such as basalt). In these cases where reactants are present in volcanic ash and / or exist as a part of volcanic ash, two kinds of volcanic ashes may be combined, with the limiting condition that the ratio of the reactants is within the ratio described herein. For example, slag and basalt (with sufficient reactant content) may be combined according to the ratio described herein. In one aspect, the sum of the proportions of the reactants and natural pozzolan or volcanic ash is 15% to 50% by weight of the mixture (e.g., 15%-50%, 15%-45%, 15-40%, 15%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values between the foregoing ranges, etc.), and wherein the proportion by weight of natural pozzolan or volcanic ash is 90% to 110% of the proportion of the reactants by weight of the mixture.
[0147] In some embodiments, the formulation or mixture may include the combined reactants and a natural pozzolan and / or pozzolan content in an amount of 40% to 80% (e.g., 40%-80%, 40%-75%, 40%-70%, 40%-65%, 40%-60%, 40%-55%, 40%-50%, 40%-45%, 45%-80%, 45%-75%, 45%-70%, 45%-65%, 45%-60%, 45 ...5%- %-50%, 50%-80%, 50%-75%, 50%-70%, 50%-65%, 50%-60%, 50%-55%, 55%-80%, 55%-75%, 55%-70%, 55%-65%, 55%-60%, 60%-80%, 60%-75%, 60%-70%, 60%-65%, 65%-80%, 65%-75%, 65%-70%, 70%-80%, 70%-75%, 75-80%, percentages between the aforementioned ranges, etc.).
[0148] In some embodiments, the formulation or mixture may include the combined reactants and natural pozzolans and / or volcanic ash in an amount of 10% to 50% (e.g., 10%-50%, 10%-45%, 10%-40%, 10%-35%, 10%-30%, 10%-25%, 10%-20%, 10%-15%, 15%-50%, 15%-45%, 15%-40%, 15%-35%, 15%-30%, 15%-25%, 15%-20%, 10%-15%, 15%-50%, 15%-45%, 15%-40%, 15%-35%, 15%-30%, 15%-25%, 15%- -20%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 20%-30%, 20%-25%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-50%, 30%-45%, 30%-40%, 30%-35%, 35%-50%, 35%-45%, 35%-40%, 40%-50%, 40%-45%, 45-50%, percentages between the aforementioned ranges, etc.). According to some embodiments, the sum of the proportions of reactants and natural pozzolans and / or volcanic ash is 40% to 70% by weight of the mixture (e.g., 40%-70%, 50%-60%, 40%-60%, 40%-50%, 40%-45%, 45%-50%, 45%-55%, 45%-60%, 45%-65%, 45%-70%, 50%-55%, 50%-65%, 50%-70%, 55%-60%, 55%-65%, 55%-70%, 60%-65%, 60%-70%, other percentages between the foregoing ranges, etc.).
[0149] In some embodiments, the curable mixture or formulation further comprises at least one accelerator. In some embodiments, the accelerator comprises at least one of magnesium chloride, magnesium nitrate and magnesium sulfate. In some embodiments, the at least one accelerator is 15% to 50% (e.g., 15%-50%, 15%-45%, 15-40%, 15%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values between the aforementioned ranges, etc.) of the proportion of the reactants by weight of the mixture.
[0150] In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 75:25wt.% to 25:75wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 65:35wt.% to 35:65wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 60:40wt.% to 40:60wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is about 50:50wt.%. The ratio can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0151] In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 75:25wt.% to 25:75wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of natural pozzolan to artificial pozzolan is 65:35wt.% to 35:65wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 60:40wt.% to 40:60wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of natural pozzolan to artificial pozzolan is about 50:50wt.%. The ratio can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0152] In embodiments, the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
[0153] In some embodiments, the cementitious mixture does not include, and may specifically exclude, MgO obtained from a calcination reaction. In some embodiments, the concrete mixture includes MgO, wherein less than 90%, 80%, 70%, 60%, 50%, 40%, 30%, 25%, 20%, 15%, 10%, or 5% of the MgO is obtained from a calcination reaction; or any subvalue or subrange between 0% and 90%.
[0154] In embodiments, the amount of natural pozzolan is in the range of about 33 wt.% to about 300 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 50 wt.% to about 200 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present is in the range of about 85 wt.% to about 115 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 90 wt.% to about 110 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 160 wt.%, 166 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 wt.%, 182 wt.%, 183 wt.%, 184 wt.%, 185 wt.%, 186 wt.%, 187 wt.%, 188 wt.%, 189 wt.%, 190 wt.%, 191 %, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0155] In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 12 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 15 wt.% to about 30 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, or 30 wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0156] In embodiments, the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 110 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 50 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 80 wt.% to about 110 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%. %, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, 60wt.%, 70wt.%, 80wt.%, 90wt.%, 100wt.%, 110wt.%; or its sub-integer, including the range between the endpoints. For example, in an embodiment, the amount of sulfate present is 31wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In other embodiments, the amount of sulfate present is 90wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). The amount can be any sub-value or sub-range therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0157] In embodiments, the amount of sodium present is in a range from about 0.1 wt. % to about 5 wt. % relative to the amount of slag (eg, ground granulated blast furnace slag). In embodiments, the amount of chloride present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.% or a sub-integer thereof. For example, in embodiments, the amount of sodium present relative to the amount of slag (eg, ground granulated blast furnace slag) is 4.5 wt.%. This amount can be any subvalue or subrange therebetween, including endpoints, and including but not limited to those specifically noted herein.
[0158] In embodiments, the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of chloride depends on the end use and the size of the batch. Without being bound by any one theory, the use of chloride contributes to the density of the batch. In embodiments, the amount of chloride present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.% or a sub-integer thereof. For example, in embodiments, the amount of chloride present relative to the amount of slag (eg, ground granulated blast furnace slag) is 1.8 wt.%. This amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0159] In embodiments, the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of phosphate present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.%, 2.5 wt.%, 2.6 wt.%, 2.7 wt.%, 2.8 wt.%, 2.9 wt.%, 3.0 wt.%, 3.1 wt.%, 3.2 wt.%, 3.3 wt.%, 3.4 wt.%, 3.5 wt.%, 3.6 %, 1.7wt.%, 1.8wt.%, 1.9wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%; or its sub-integer. The amount can be any sub-value or sub-range therebetween, including endpoints, and including but not limited to those specifically indicated herein.
[0160] In one aspect, embodiments of the present invention provide a cementitious mixture comprising: (a) an aqueous solution comprising water and a natural pozzolan; and (b) ground granulated blast furnace slag; wherein the cementitious mixture has a pH of at least 8. In one aspect, embodiments of the present invention provide a cementitious mixture comprising: (a) an aqueous solution comprising water; (b) a natural pozzolan; and (c) an artificial pozzolan; wherein the cementitious mixture has a pH of at least 8. In one aspect, embodiments of the present invention provide a cementitious mixture comprising: (a) an aqueous solution comprising water and a pozzolan; and b) MgO; wherein the cementitious mixture has a pH of at least 8. In one aspect, embodiments of the present invention provide a cementitious mixture comprising: (a) an aqueous solution comprising water and a pozzolan; and (b) Mg(OH)2; wherein the cementitious mixture has a pH of at least 8.
[0161] In embodiments, the cementitious mixture has a pH of at least 8, at least 9, at least 10, at least 11, at least 12, or at least 13. In embodiments, the cementitious mixture has a pH of 8 to 14, 8 to 13, 8 to 12, 8 to 11, 8 to 10, or 8 to 9. In embodiments, the cementitious mixture has a pH of 9 to 14, 9 to 13, 9 to 12, 9 to 11, or 9 to 10. In embodiments, the cementitious mixture has a pH of 10 to 14, 10 to 13, 10 to 12, or 10 to 11. In embodiments, the cementitious mixture has a pH of 11 to 14, 11 to 13, or 11 to 12. In embodiments, the cementitious mixture has a pH of 12 to 14 or 12 to 13. In embodiments, the cementitious mixture has a pH of 13 to 14. The pH may be any subvalue or subrange therebetween, including endpoints, and including but not limited to those specifically noted herein. In embodiments, the pH is the pH of seawater. In embodiments, the pH of the seawater is about 8, such as about 8.1.
[0162] In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 75:25wt.% to 25:75wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 65:35wt.% to 35:65wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 60:40wt.% to 40:60wt.%. In an embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of natural pozzolan to ground granulated blast furnace slag is about 50:50wt.%. This amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0163] In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 75:25wt.% to 25:75wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 70:30wt.% to 30:70wt.%. In another embodiment, the ratio of natural pozzolan to artificial pozzolan is 65:35wt.% to 35:65wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 60:40wt.% to 40:60wt.%. In an embodiment, the ratio of natural pozzolan to artificial pozzolan is 55:45wt.% to 45:55wt.%. In another embodiment, the ratio of natural pozzolan to slag is about 50:50wt.%. This amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically indicated herein.
[0164] In embodiments, the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
[0165] In some embodiments, the cementitious mixture does not include MgO, and may specifically exclude that obtained from a calcination reaction. In some embodiments, the cementitious mixture includes MgO, wherein less than 90%, 80%, 70%, 60%, 50%, 40%, 30%, 25%, 20%, 15%, 10%, or 5% of MgO is obtained from a calcination reaction; or any subvalue or subrange between 0% and 90%. The amount may be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0166] In embodiments, the amount of natural pozzolan is in the range of about 33 wt.% to about 300 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 50 wt.% to about 200 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present is in the range of about 85 wt.% to about 115 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 90 wt.% to about 110 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 151 wt.%, 152 wt.%, 153 wt.%, 154 wt.%, 155 wt.%, 156 wt.%, 157 wt.%, 158 wt.%, 159 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 169 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 %, 165wt.%, 170wt.%, 175wt.%, 180wt.%, 185, 190wt.%, 195wt.%, 200wt.%, 205wt.%, 210wt.%, 215wt.%, 220wt.%, 230wt.%, 235wt.%, 240wt.%, 245wt.%, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0167] In embodiments, the amount of natural pozzolan relative to the amount of artificial pozzolan ranges from about 33 wt.% to about 300 wt.%. In some embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 50 wt.% to about 200 wt.%. In embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 85 wt.% to about 115 wt.%. In some embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 90 wt.% to about 110 wt.%. In embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 wt.%, 182 %, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%. The amount can be any subvalue or subrange therebetween, including endpoints, and includes but is not limited to those specifically noted herein.
[0168] In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 12 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 15 wt.% to about 30 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, or 30 wt.%.
[0169] In embodiments, the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 110 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 50 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 80 wt.% to about 110 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%. %, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%, 70 wt.%, 80 wt.%, 90 wt.%, 100 wt.%, 110 wt.%; or its sub-integer, including the range between the endpoints. For example, in embodiments, the amount of sulfate present is 31 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In other embodiments, the amount of sulfate present is 90 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag).
[0170] In embodiments, the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In embodiments, the amount of chloride depends on the end use and the size of the batch. Without being bound by any one theory, the use of chloride contributes to the density of the batch. In embodiments, the amount of chloride present relative to the amount of slag (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.% or a sub-integer thereof. For example, in embodiments, the chloride is present in an amount of 1.8 wt. % relative to the amount of slag (eg, ground granulated blast furnace slag).
[0171] In embodiments, the process is effectively operated at ambient pressure and / or gas temperature. For example, in some embodiments, the curing step is performed at ambient pressure. In some embodiments, the pressure is about 0.5 to about 10 atm, for example, about 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 3, 4, 5, 6, 7, 8, 9 or 10 atm. In some embodiments, the pressure exceeds the curing step or is applied after the curing step. In some embodiments, the temperature is about 15 ° C to about 80 ° C, for example, about 15 ° C, 20 ° C, 25 ° C, 30 ° C, 35 ° C, 40 ° C, 45 ° C, 50 ° C, 55 ° C, 60 ° C, 65 ° C, 70 ° C, 75 ° C or 80 ° C. In some embodiments, the process includes a cooling step. In embodiments, the cooling temperature is 30°C, 29°C, 28°C, 27°C, 26°C, 25, 24°C, 23°C, 22°C, 21°C, 20°C, 19°C, 18°C, 17°C, 16°C, 15°C, 14°C, 13°C, 12°C, 11°C, 10°C, 9°C, 8°C, 7°C, 6°C, 5°C, 4°C, 3°C, 2°C, 1°C or 0°C.
[0172] In an embodiment, the poured cementitious mixture comprises at least one accelerator, wherein the at least one accelerator comprises at least one of: magnesium chloride, magnesium nitrate, and magnesium sulfate. In some embodiments, the at least one accelerator comprises sodium hexametaphosphate ((NaPO3)6 or SHMP). In some embodiments, sodium hexametaphosphate is excluded. In some embodiments, when non-magnesium-based accelerators (e.g., SHMP) are included in the mixture, the content of such non-magnesium-based accelerators is relatively small. For example, in some configurations, the content of such non-magnesium-based accelerators in the mixture is less than 2% (e.g., 0%-2%, 0.1%-2%, 0%-1%, 0.1%-1%, 1%-2%, values between the foregoing ranges, etc.) based on the weight of the entire dry mixture.
[0173] In embodiments, at least one accelerator comprises magnesium chloride in the form of MgCl2·6H2O. In embodiments, at least one accelerator comprises magnesium nitrate in the form of Mg(NO3)2·6H2O. In one aspect, at least one accelerator further comprises magnesium sulfate in the form of MgSO4·7H2O. In embodiments, the poured cementitious mixture comprises at least two accelerators. In embodiments, the poured cementitious mixture comprises at least two accelerators. In embodiments, the poured cementitious mixture comprises at least three accelerators. In embodiments, the poured cementitious mixture comprises three accelerators. In embodiments, at least one accelerator is present in an amount of about 1 wt.% to about 5 wt.%. In embodiments, the accelerator is present in an amount of about 1.0 wt.%, about 1.1 wt.%, about 1.2 wt.%, about 1.3 wt.%, about 1.4 wt.%, about 1.5 wt.%, about 1.6 wt.%, about 1.7 wt.%, about 1.8 wt.%, about 1.9 wt.%, about 2.0 wt.%, about 2.1 wt.%, about 2.2 wt.%, about 2.3 wt.%, about 2.4 wt.%, about 2.5 wt.%, about 2.6 wt.%, about 2.7 wt.%, about 2.8 wt.%, about 2.9 wt.%, about 3.0 wt.%, about 3.1 wt.%, about 3.2 wt.%, about 3.3 wt.%, about 3.4 wt.%, about 3.5 wt.%, about 3.6 wt.%, about 3.7 wt.%, about 3.8 wt.%, about 3.9 wt.%, about 4. %, about 4.8wt.%, about 4.0wt.%, about 4.1wt.%, about 4.2wt.%, about 4.3wt.%, about 4.4wt.%, about 4.5wt.%, about 4.6wt.%, about 4.7wt.%, about 4.8wt.%, about 4.9wt.% or about 5.0wt.%. In an embodiment, at least one promoter is present in an amount of about 1 wt.%-5 wt.%, 1 wt.%-4.5 wt.%, 1 wt.%-4 wt.%, 1 wt.%-3.5 wt.%, 2 wt.%-5 wt.%, 2 wt.%-4.5 wt.%, 2 wt.%-4 wt.%, 2 wt.%-3.5 wt.%, 2.5 wt.%-5 wt.%, 2.5 wt.%-4.5 wt.%, 2.5 wt.%-4 wt.%, 2.5 wt.%-3.5 wt.%, 2.5 wt.%-3 wt.%, 3 wt.%-3.5 wt.%, or values between the foregoing ranges (including endpoints).
[0174] In one aspect, at least one promoter comprises magnesium chloride in the form of MgCl2·6H2O or magnesium nitrate in the form of Mg(NO3)2·6H2O, wherein the proportion of MgCl2·6H2O or Mg(NO3)2·6H2O by weight is 0.25% to 30% (e.g., 0%, 0%-30%, 0%-25%, 0%-20%, 0%-15%, 0%-10%, 0%-5%, 1%-30%, 0.25%-25%, 0.25%-20%, 0.25%-15%, 0.25%-10%, 0.25 %-5%, 2%-30%, 2%-25%, 2%-15%, 2%-12%, 2%-10%, 2%-8%, 2%-6%, 2%-5%, 2%-4%, 2%-3%, 3%-30%, 3%, 25%, 3%, 15%, 3%-12%, 3%-10%, 3%-8%, 3%-6%, 3%-5%, 3%-4%, 5%-30%, 5%-25%, 5%-20%, 5%-15%, 5%-12%, 5%-10%, 10%-30%, 10%-20%, 15%-25%, 15%-30%, values between the aforementioned ranges, etc.). In an embodiment, the proportion of MgCl2·6H2O or Mg(NO3)2·6H2O by weight is 80% to 120% of the proportion of the reactants by weight of the mixture (e.g., 80%-120%, 90%-110%, 95%-105%, 98%-102%, 80%-100%, 85%-100%, 90%-100%, 95%-100%, 80%-90%, 85%-95%, 100%-120%, 100%-115%, 100%-110%, 100%-105%, 105%-115%, 105%-120%, values between the foregoing ranges, etc.).
[0175] In one aspect, at least one promoter further comprises magnesium sulfate in the form of MgSO4.7H2O, wherein the proportion of MgSO4.7H2O by weight is 5% to 70% (e.g., 5%-70%, 5%-65%, 5%-60%, 5%-55%, 5%-50%5%-45%, 15-40%, 15%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values between the foregoing ranges, etc.) of the proportion of the reactants by weight of the mixture. The proportion by weight is 90% to 140% of the proportion of the reactants by weight of the mixture (e.g., 90%-140%, 90%-130%, 90%-120%, 90%-110%, 95%-105%, 98%-102%, 80%-100%, 85%-100%, 90%-100%, 95%-100%, 80%-90%, 85%-95%, 100%-120%, 100%-115%, 100%-110%, 100%-105%, 105%-115%, 105%-120%, 105-130%, 105-140%, values between the foregoing ranges, etc.).
[0176] In one aspect, the curable mixture further comprises at least one accelerator, wherein the at least one accelerator comprises magnesium chloride in the form of MgCl2.6H2O or magnesium nitrate in the form of Mg(NO3)2.6H2O. In one aspect, the proportion of MgCl2.6H2O or Mg(NO3)2.6H2O by weight is 80% to 120% of the proportion of the reactants by weight of the mixture.
[0177] In one aspect, the curable mixture further comprises at least one accelerator, wherein the at least one accelerator comprises magnesium sulfate in the form of MgSO4.7H2O. In some embodiments, the proportion of MgSO4.7H2O by weight is 90% to 140% of the proportion of the reactants by weight of the mixture.
[0178] In one aspect, the proportion of at least one accelerator by weight is 5% to 70% of the proportion of the reactants by weight of the mixture, the weight of the mixture being determined by the mass of the mixture. In one aspect, the proportion of at least one accelerator by weight is 80% to 145% of the proportion of the reactants by weight of the mixture, the weight of the mixture being determined by the mass of the mixture.
[0179] According to some embodiments, at least one accelerator comprises MgCl2·6H2O or Mg(NO3)2·6H2O, wherein the proportion by weight of MgCl2·6H2O or Mg(NO3)2·6H2O is 0.1%-30%, 1%-30%, 2% to 30% (e.g., 2%-12%, 2%-10%, 2%-8%, 2%-6%, 2%-5%, 2%-4%, 2%-3%, 3%-12%, 3%-10%, 3%-8%, 3%-6%, 3%-5%, 3%-4%, 5%-12%, 5%-10%, 6%-1 0%, 6%-8%, values between the aforementioned ranges, etc.), and the at least one promoter further comprises magnesium sulfate in the form of MgSO4·7H2O, wherein the proportion of MgSO4·7H2O by weight is 15% to 50% (e.g., 15%-50%, 15%-45%, 15-40%, 15%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values between the aforementioned ranges, etc.) of the proportion of the reactants by weight of the mixture.
[0180] In one aspect, at least one accelerator does not include phosphate or other phosphorus-based materials. In some embodiments, at least one accelerator includes a phosphate-based accelerator, wherein the phosphate-based accelerator is present in a weight ratio of 0.1% to 5% of the reactants by weight of the mixture. In some embodiments, the accelerator includes a phosphate-based accelerator, wherein the phosphate-based accelerator is present in a weight ratio of 0.1% to 5% of the reactants by weight of the mixture (e.g., 0.1%-5%, 0.5%-5%, 1-5%, 1.5%-5%, 2%-5%, 2%-4.5%, 2%-4%, 2%-3.5%, 2.5%-5%, 2.5-4.5%, 2.5%-4%, 2.5%-3.5%, 2.5%-3%, 3%-3.5%, 3%-5%, 4%-5%, values between the foregoing ranges, etc.).
[0181] In one aspect, at least one promoter can be provided in a dry crystalline form, such as, for example, MgCl2.6H2O, Mg(NO3)2.6H2O, and / or MgSO4.7H2O. However, in other configurations, if necessary or desired, at least one promoter can be provided in the mixture as part of a solution (e.g., in liquid form).
[0182] According to some embodiments, the mixture is configured to be combined with water to produce a curable paste, wherein the amount of water used to produce the curable paste is 25% to 125% by mass of the amount of reactants in the mixture. In some embodiments, the amount of water (and / or other liquids) added to the dry mixture to form a curable product is 75% to 125% (e.g., 75-125, 80-120, 85-115, 90-110, 95-105, 75-100, 100-125%, percentages between the foregoing ranges, etc.) of the mass of MgO. In embodiments, the amount of water used to produce the settable paste is 75% to 125% (e.g., 75%-125%, 75%-120%, 75%-115%, 75%-110%, 75%-105%, 75%-100%, 75%-95%, 75%-90%, 75%-85%, 75%-80%, 80%-125%) of the amount of MgO in the mixture by mass. 5%, 80%-120%, 80%-115%, 80%-110%, 80%-105%, 80%-100%, 80%-95%, 80%-90%, 80%-85%, 85%-125%, 85%-120%, 85%-115%, 85%-110%, 85%-105%, 85%-100%, 85%-95%, 85%-90 %, 90%-125%, 90%-120%, 90%-115%, 90%-110%, 90%-105%, 90%-100%, 90%-95%, 95%-125%, 95%-120%, 95%-115%, 95%-110%, 95%-105%, 95%-100%, 100%-125%, 100%-120%, 1 00%-115%, 100%-110%, 100%-105%, 105%-125%, 105%-120%, 105%-115%, 105%-110%, 110%-125%, 110%-120%, 110%-115%, 115%-125%, 115%-120%, 120%-125%, values between the aforementioned ranges, etc.).
[0183] In embodiments, the concrete replacement material produced by combining the mixture with water is suitable for long-term contact with reinforcing steel, mesh, steel, and other corrosive materials.
[0184] In embodiments, the artificial stone-like material produced by combining the mixture with water is suitable for long-term contact with reinforcing steel, mesh, steel, and other materials susceptible to corrosion.
[0185] In embodiments, the artificial stone-like material produced by combining the mixture with water is suitable for long-term contact with reinforcing steel, mesh, steel, and other materials susceptible to corrosion.
[0186] In an embodiment, the mixture further comprises at least one filler material or other additive selected from the group consisting of pumice or other volcanic rock or material, sand, aggregate (e.g., fine aggregate, coarse aggregate, intermediate aggregate, other types of aggregate, etc.), lightweight aggregate, talc, other clay materials, fibers (e.g., steel and / or other metal fibers, polypropylene and / or other polymeric fibers, glass fibers, asbestos fibers, carbon fibers, organic fibers, etc.), glass fiber reinforced plastics (GFRP), other reinforcing polymers, blends or other additives that promote fire resistance, waterproofing, corrosion resistance / inhibition, processability and / or one or more other properties of the final cured product (e.g., MasterPel, RheoCell, MasterCell, etc.), sodium naphthalenesulfonate formaldehyde (SNF) and / or other surfactants, plasticizers, pigments, dyes and other color additives, titanium dioxide, other minerals, other natural or synthetic materials, other filler materials and / or the like. In embodiments, fillers and / or other additives include, but are not limited to, non-cementitious slag (e.g., air-cooled slag or electric arc furnace slag), non-Class C fly ash (e.g., Class F fly ash), silica fume, nano-silica, fine silica glass, other silicon-based materials, waste glass, ground glass, other glass-containing materials, post-consumer materials, other waste materials, fine aggregate, intermediate aggregate, coarse aggregate, other types of aggregate, pumice or other volcanic rocks or materials. In some embodiments, fillers and / or other additives are included to react with other components of the mixture and / or to provide a certain beneficial feature or characteristic to the resulting slurry (e.g., once the mixture is combined with water) and / or the final cured product. For example, in some embodiments, such materials (e.g., air-cooled slag, other non-cementitious slag, Class F fly ash, other non-cementitious fly ash, volcanic ash, silica fume, etc.) can be used to reduce the permeability of the resulting slurry or cured product. In some embodiments, such materials help plug or otherwise fill the holes or other cavities in the resulting slurry and cured product. According to some configurations, a mixture or formulation comprising a material providing one or more benefits or other advantages to the resulting slurry or cured product may be referred to as a ternary mixture. In some embodiments, the non-cementitious component included in the ternary mixture meets the requirements of ASTM C595. In some embodiments, fillers and / or other additives are included so as to provide one or more other benefits and advantages in addition to or in lieu of reducing permeability. For example, one or more additives listed above can promote fire resistance, waterproofing, corrosion resistance / inhibition, workability and / or one or more other characteristics of the final cured product. In some embodiments, fillers such as aggregate (e.g., coarse aggregate, intermediate aggregate, fine aggregate, etc.), clay, pumice or other volcanic rocks or materials, sand, talc, other clay materials, etc., exist only as fillers.Such materials can provide the mixture and resulting neat and cured products with desired or required density and structural properties.
[0187] In embodiments of cementitious mixtures, the amount of natural pozzolan and ground granulated blast furnace slag in the formulation can be relatively equal to each other in terms of weight %. For example, the ratio of the amount of natural pozzolan to ground granulated blast furnace slag can range from about 75:25 to about 25:75. In embodiments, the ratio of natural pozzolan to ground granulated blast furnace slag is 75:25, 70:30, 65:35, 60:40, 59:41, 58:42, 57:43, 56:44, 55:45, 54:46, 53:47, 52:48, 51:49, 50:50, 49:51, 48:52, 47:53, 46:54, 45:55, 44:56, 43:57, 42:58, 41:59, 40:60, 35:65, 30:70 or 25:75.
[0188] In embodiments of cementitious mixtures, the amounts of natural pozzolan and artificial pozzolan in the formulation may be relatively equal to each other in terms of weight %. For example, the ratio of the amount of natural pozzolan to artificial pozzolan may range from about 75:25 to about 25:75. In embodiments, the ratio of natural pozzolan to artificial pozzolan is 75:25, 70:30, 65:35, 60:40, 59:41, 58:42, 57:43, 56:44, 55:45, 54:46, 53:47, 52:48, 51:49, 50:50, 49:51, 48:52, 47:53, 46:54, 45:55, 44:56, 43:57, 42:58, 41:59, 40:60, 35:65, 30:70, or 25:75.
[0189] In embodiments, the amount of natural pozzolan is in the range of about 33 wt.% to about 300 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 50 wt.% to about 200 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present is in the range of about 85 wt.% to about 115 wt.% relative to the amount of ground granulated blast furnace slag. In some embodiments, the amount of natural pozzolan present is in the range of about 90 wt.% to about 110 wt.% relative to the amount of ground granulated blast furnace slag. In embodiments, the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 151 wt.%, 152 wt.%, 153 wt.%, 154 wt.%, 155 wt.%, 156 wt.%, 157 wt.%, 158 wt.%, 159 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 169 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 %, 165wt.%, 170wt.%, 175wt.%, 180wt.%, 185, 190wt.%, 195wt.%, 200wt.%, 205wt.%, 210wt.%, 215wt.%, 220wt.%, 230wt.%, 235wt.%, 240wt.%, 245wt.%, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33%wt.% and 300wt.%.
[0190] In embodiments, the amount of natural pozzolan relative to the amount of artificial pozzolan ranges from about 33 wt.% to about 300 wt.%. In some embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 50 wt.% to about 200 wt.%. In embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 85 wt.% to about 115 wt.%. In some embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 90 wt.% to about 110 wt.%. In embodiments, the amount of natural pozzolan present relative to the amount of artificial pozzolan is 33 wt.%, 34 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, 60 wt.%, 65 wt.%, 70 wt.%, 75 wt.%, 80 wt.%, 85 wt.%, 90 wt.%, 95 wt.%, 100 wt.%, 105 wt.%, 110 wt.%, 115 wt.%, 120 wt.%, 125 wt.%, 130 wt.%, 135 wt.%, 140 wt.%, 145 wt.%, 150 wt.%, 160 wt.%, 161 wt.%, 162 wt.%, 163 wt.%, 164 wt.%, 165 wt.%, 166 wt.%, 167 wt.%, 168 wt.%, 170 wt.%, 171 wt.%, 172 wt.%, 173 wt.%, 174 wt.%, 175 wt.%, 176 wt.%, 177 wt.%, 178 wt.%, 179 wt.%, 180 wt.%, 181 wt.%, 182 %, 250wt.%, 265wt.%, 270wt.%, 275wt.%, 280wt.%, 285wt.%, 290wt.%, 295wt.%, 300wt.%; or any subvalue or subrange between 33wt.% and 300wt.%.
[0191] In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 2 wt.% to about 12 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is in the range of about 15 wt.% to about 30 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of nitrate present is about 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, or 30 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag).
[0192] In embodiments, the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 110 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 20 wt.% to about 50 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present is in the range of about 80 wt.% to about 110 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of sulfate present relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag) is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, 16 wt.%, 17 wt.%, 18 wt.%, 19 wt.%, 20 wt.%, 21 wt.%, 22 wt.%, 23 wt.%, 24 wt.%, 25 wt.%, 26 wt.%, 27 wt.%, 28 wt.%, 29 wt.%, 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, 40 wt.%, 41 wt.%, 42 wt.%, 43 wt.%, 44 wt.%, 45 wt.%, 46 wt.%, 47 wt.%, 48 wt.%, 49 wt.%, 50 wt.%, 51 wt.%, 52 wt.%, 53 wt.%, 54 wt.%, 55 wt.%, 56 wt.%, 57 wt.%, 58 wt.%, 59 wt %, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, 60wt.%, 70wt.%, 80wt.%, 90wt.%, 100wt.%, 110wt.%; or its sub-integer, including the range between the endpoints. For example, in embodiments, the amount of sulfate present is 31wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag). In other embodiments, the amount of sulfate present is 90wt.% relative to the amount of slag (e.g., ground granulated blast furnace slag).
[0193] In embodiments, the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of chloride depends on the end use and the size of the batch. Without being bound by any one theory, the use of chloride contributes to the density of the batch. In embodiments, the amount of chloride present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, or a sub-integer thereof, relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). For example, in embodiments, the chloride is present in an amount of 1.8 wt. % relative to the amount of slag (eg, ground granulated blast furnace slag).
[0194] In embodiments, the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of artificial pozzolan (e.g., ground granulated blast furnace slag). In embodiments, the amount of phosphate present is about 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.%, 2.5 wt.%, 2.6 wt.%, 2.7 wt.%, 2.8 wt.%, 2.9 wt.%, 3.0 wt.%, 3.1 wt.%, 3.2 wt.%, 3.3 wt.%, 3.4 wt.%, 3.5 wt.%, 3.6 wt.%, 3.7 wt.%, 3.8 wt.%, 3.9 wt.%, 4.1 wt.%, 4.2 wt.%, 4.3 wt.%, 4.4 wt.%, 4.5 wt.%, 4.6 wt.%, 4.7 wt.%, 4.8 wt.%, 4.9 wt.%, 4.1 %. .6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%; or a sub-integer thereof.
[0195] In one aspect, the proportion of volcanic ash by weight is 80% to 120% of the proportion of reactants by weight of the mixture. In one aspect, the sum of the proportions of reactants and volcanic ash comprises at least 12% by weight of the mixture. In an embodiment, the sum of the proportions of reactants and natural volcanic ash or volcanic ash is 15% to 50% by weight of the mixture (e.g., 15%-50%, 15%-45%, 15-40%, 15%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values between the aforementioned ranges, etc.), and wherein the proportion of natural volcanic ash or volcanic ash by weight is 90% to 110% of the proportion of reactants by weight of the mixture. In one aspect, the sum of the proportions of the reactants and natural pozzolans and / or volcanic ash is 40% to 70% by weight of the mixture. In some embodiments, the proportion of natural pozzolans and / or volcanic ash by weight is 90% to 110% of the proportion of the reactants by weight of the mixture.
[0196] In one aspect, the proportion of at least one promoter by weight is 10% to 70% of the proportion of the reactants by weight of the mixture (e.g., 10%-70%, 10%-65%, 10%-60%, 10%-55%, 10%-50%, 10%-45%, 10%-40%, 10%-35%, 20%-50%, 20%-45%, 20%-40%, 20%-35%, 25%-50%, 25%-45%, 25%-40%, 25%-35%, 25%-30%, 30%-35%, values in between the foregoing ranges, etc.).
[0197] In embodiments, the present application encompasses a variety of end uses of concrete alternative materials. Those uses include, but are not limited to, residential and commercial construction (e.g., for columns, beams and other load-bearing components), walls and other building panels (e.g., including non-load-bearing components), airports, dams, levees, bridges, tunnels, ports, refineries and other industrial sites, parking structures, roads, sidewalks, tiles and other floors, paving materials, flower pots, household items, pipelines, passages, countertops and / or similar places thereof. According to the ability of the final cured product not to damage steel or other metals, one or more formulations or mixtures are suitable for applications where it is desired or required to tensilely enhance (e.g., to prevent or reduce the possibility of cracking, fracture and / or other damage to the cured product). The purposes of the present application also encompass precast materials, such as panels for buildings. Other non-structural uses of the present application provided herein may be islands in the kitchen, decorative garden structures (e.g., basins, benches, flower pots, basins, etc.), tiles, decorative floors, furniture, bathroom bathtubs, sinks, tables, hearths, basins, pool decks or any construction or decorative application where concrete materials may be used.
[0198] According to some embodiments, the cementitious mixture formed by combining any of the mixtures disclosed herein with water comprises a density equal to or substantially equal to the density of neat Portland cement paste. In some embodiments, the density of the cementitious mixture is 80% to 120% (e.g., 80%-120%, 90%-110%, 95%-105%, 98%-102%, 80%-100%, 85%-100%, 90%-100%, 95%-100%, 80%-90%, 85%-95%, 100%-120%, 100%-115%, 100%-110%, 100%-105%, 105%-115%, 105%-120%, values between the foregoing ranges, etc.) of the density of neat Portland cement paste.
[0199] In addition, according to some embodiments, the cementitious mixture formed by combining any of the mixtures disclosed herein with water comprises a leaching rate equal to substantially equal to that of Portland cement paste. In some embodiments, the leaching rate of the cementitious mixture is 80% to 120% of the leaching rate of Portland cement paste. According to some embodiments, for one or more mixture configurations disclosed herein, during and / or after curing, the leaching rate of the components (MgCl2, Mg(NO3)2, MgSO4, water, anhydrous and / or other compounds having the same, etc.) is equal to or lower than the leaching rate of known cements (e.g., Portland cement, MgO or other magnesium oxide cements, etc.). In some embodiments, the leaching rate by mass can be reduced by 0%-10% (e.g., 0-10, 0-5, 2-8, 2-10, 5-10, 2-5, 5-8, 1-9%, percentages between the aforementioned ranges, etc.) relative to known cements. In some embodiments, one or more mixture configurations disclosed herein are equal to or substantially equal to the leaching rate of known cements (e.g., Portland cement, MgO or other magnesium oxide cements, etc.). In other configurations, however, the leaching rate by mass may be reduced by more than 0%-10% (e.g., 10-15, 15-20 / 20-30%, above 30%, etc.).
[0200] Furthermore, according to some embodiments, the cementitious mixture formed by combining any of the mixtures disclosed herein with water comprises an elastic modulus equal to substantially equal to that of neat Portland cement paste. According to some embodiments, the cementitious mixture formed by combining any of the mixtures disclosed herein with water comprises an elastic modulus equal to substantially equal to that of neat Portland cement paste.In some embodiments, the elastic modulus of the cementitious mixture is 50% to 200% of the elastic modulus of neat Portland cement paste (e.g., 50-200, 50-190, 50-180, 50-170, 50-160, 50-150, 50-140, 50-130, 50-120, 50-110, 50-100, 50-90, 50-80, 50-70, 50-60, 60-200, 60-190, 60-180, 60-170, 60-160, 60-150, 60-140, 60-130, 60-120, 60-110, 60-100, 60-90, 60-80, 60-70, 70 -200, 70-190, 70-180, 70-170, 70-160, 70-150, 70-140, 70-130, 70-120, 70-110, 70-100, 70-90, 70-80, 80-200, 80-190, 80-180, 80-170, 80-160, 80-150, 80-140, 80-130, 80-120, 80-110, 80-100, 80-90, 90-200, 90-190, 90-180, 90-170, 90-160, 90-150, 90-140, 90-130, 90-120, 90-110, 90-10 0, 100-200, 100-190, 100-180, 100-170, 100-160, 100-150, 100-140, 100-130, 100-120, 100-110, 110-200, 110-190, 110-180, 110-170, 110-160, 110-150, 110-140, 110-130, 110-120, 120-200, 120-190, 120-180, 120-170, 120-160, 120-150, 120-140, 120-130, 130-200, 130-190, 130-180, 130 -170, 130-160, 130-150, 130-140, 140-200, 140-190, 140-180, 140-170, 140-160, 140-150, 150-200, 150-190, 150-180, 150-170, 150-160, 160-200, 160-190, 160-180, 160-170, 170-200, 170-190, 170-180, 180-200, 180-190, 190-200, 95-105, 85-115, 75-125, 65-135, 55-145, values between the aforementioned values and ranges, etc.).In some embodiments, the elastic modulus of the cementitious mixture formed by combining any of the mixtures disclosed herein with water is between 3 (106) and 5 (106) (e.g., between 3 (106) and 5 (106), between 3.0 (106) and 3.5 (106), between 3.5 (106) and 4.0 (106), between 4.0 (106) and 4.5 (106), between 4.5 (106) and 5.0 (106), between 3 (106) and 4 (106), between 3.0 (106) and 4.5 (106), between 3.5 (106) and 5.0 (106), between 3.5 (106) and 4.5 (106)). 06), 3.0(106), 3.1(106), 3.2(106), 3.3(106), 3.4(106), 3.5(106), 3.6(106), 3.7(106), 3.8(106), 3.9(106), 4.0(106), 4.1(106), 4.2(106), 4.3(106), 4.4(106), 4.5(106), 4.6(106), 4.7(106), 4.8(106), 4.9(106), 5.0(106) psi, values between the above values and ranges, etc.) psi.
[0201] In addition, according to some embodiments, the settable slurry formed by combining any of the mixtures disclosed herein with water comprises a Poisson's ratio that is equal to substantially equal to that of a Portland cement slurry. In some embodiments, the Poisson's ratio of the settable slurry is between 70% and 150% (e.g., 70%-150%, 70%-140%, 70%-130%, 70%-120%, 70%-110%, 70%-100%, 70%-90%, 70%-80%, 80%-150%, 80%-140%, 80%-130%, 80%-120%, 80%-110%, 80%-100%, 80%-90%, 90%-150%, 90%-140%, 90%-130%, 90%-120 %, 90%-110%, 90%-100%, 100%-150%, 100%-140%, 100%-130%, 100%-120%, 100%-110%, 110%-150%, 110%-140%, 110%-130%, 110%-120%, 120%-150%, 120%-140%, 120%-130%, 130%-150%, 130%-140%, 140%-150%, 95%-105%, 85%-115%, 75%-125%, percentages between the aforementioned ranges, etc.). In some embodiments, the settable slurry formed by combining any of the mixtures disclosed herein with water has a Poisson's ratio of 0.15 to 0.30 (e.g., 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.15-0.25, 0.15-0.20, 0.25-0.30, 0.20-0.25, 0.20-0.27, 0.20-0.30, values between the foregoing values and ranges, etc.). III. method
[0202] In one aspect, the present invention provides a method for manufacturing a process and / or product of a negative carbon dioxide emission concrete substitute material, the manufacturing method comprising (a) mixing a slurry comprising water, natural pozzolan, nitrate, sulfate, sodium, chloride and / or phosphate with ground granulated blast furnace slag to form a cementitious mixture; (b) pouring the cementitious mixture into a structural component mold to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) in the structural mold to form a negative carbon dioxide emission concrete substitute material. In one aspect, the present invention provides a method for manufacturing a process and / or product of a negative carbon dioxide emission concrete substitute material, the manufacturing method comprising (a) mixing a slurry comprising water, natural pozzolan, nitrate, sulfate, sodium, chloride and / or phosphate with artificial pozzolan to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form a negative carbon dioxide emission concrete substitute material. In one aspect, the present invention provides a method for manufacturing a process and / or product of a negative CO2 emission concrete substitute material, the manufacturing method comprising (a) mixing a slurry comprising water, volcanic ash, nitrate, sulfate, sodium, chloride and / or phosphate with MgO to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form a negative CO2 emission concrete substitute material. In one aspect, the present invention provides a method for manufacturing a process and / or product of a negative CO2 emission concrete substitute material, the manufacturing method comprising (a) mixing a slurry comprising water, volcanic ash, nitrate, sulfate, sodium, chloride and / or phosphate with Mg(OH)2 to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form a negative CO2 emission concrete substitute material.
[0203] In one aspect, provided herein is a method for manufacturing a process and / or product of an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing a slurry comprising water, natural pozzolan, nitrate, sulfate, sodium, chloride and / or phosphate with ground granulated blast furnace slag to form a cementitious mixture; (b) pouring the cementitious mixture into a structural component mold to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) in the structural mold to form an artificial stone-like material with negative carbon dioxide emissions. In one aspect, provided herein is a method for manufacturing a process and / or product of an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing a slurry comprising water, natural pozzolan, nitrate, sulfate, sodium, chloride and / or phosphate with artificial pozzolan to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form an artificial stone-like material with negative carbon dioxide emissions. In one aspect, the present invention provides a method for producing a process and / or product of an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing a slurry comprising water, volcanic ash, nitrate, sulfate, sodium, chloride and / or phosphate with MgO to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form an artificial stone-like material with negative carbon dioxide emissions. In one aspect, the present invention provides a method for producing a process and / or product of an artificial stone-like material with negative carbon dioxide emissions, the method comprising (a) mixing a slurry comprising water, volcanic ash, nitrate, sulfate, sodium, chloride and / or phosphate with Mg(OH)2 to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; and then (c) curing the poured cementitious mixture from step (b) to form an artificial stone-like material with negative carbon dioxide emissions.
[0204] In another aspect, the present invention encompasses a method for making a wall or slab of an artificial stone-like material with negative carbon dioxide emissions. In an embodiment, the method may include, but is not limited to: (1) extruding a clay extruder through a die into the final shape of a wall or slab; (2) extruding a clay extruder through a die into a thin plate having a thickness equal to or greater than the final thickness of the wall or slab and a width that allows for the width of one or more walls or slabs. The thin plate is formed into the shape of the final wall or slab by placing the thin plate on the lower half of a vertical press or passing the thin plate through a forming calender; (3) extruding a cylindrical material block, which is then formed into the final wall or slab shape between the bottom and top dies in a vertical press or similar device; or (4) mixing a rheology-modifying material and placing a limited amount of material block, which is then formed into the final wall or slab between the bottom and top dies in a vertical press or similar device.
[0205] In embodiments, any of the foregoing methods may solidify within a few hours afterwards. In embodiments, solidification occurs within about 2 hours to about 48 hours.
[0206] In an embodiment, the mechanical properties are modified by adding fiber reinforcement materials (such as cellulose fibers, glass fibers, plastic fibers, polypropylene fibers, polyvinyl alcohol (PVA) fibers, homopolymer acrylic fibers or alkali-resistant fibers, natural fibers, or combinations thereof) to produce a ductile (non-brittle) material.
[0207] In embodiments, the artificial stone-like material tiles may be rendered water resistant by including a water repellent silane and / or an oil repellent silane in the product mix or by applying a state of the art known water resistant surface coating. Example
[0208] The examples provided herein include compositions of cementitious materials comprising natural and artificial pozzolans, such as ground granulated blast furnace slag, and / or MgO or Mg(OH)2. It will be appreciated by those skilled in the art that the example compositions are non-limiting and can be adjusted based on factors such as heat and humidity to achieve properties such as compressive strength, flexural strength, elastic modulus, low degradation, and CO2 absorption as contemplated by the present application. The application and examples illustrate that the resulting effective variables for achieving these properties include sulfates, nitrates, chlorides, and pozzolans, such as natural pozzolans.
[0209] Materials and Methods. Table 1. Composition A Table 2. Properties of Composition A characteristic value 1 day curing strength >1000psi 7 days curing strength >3000psi 28 days curing strength >5000psi Table 3. Composition B Table 4. Properties of Composition B characteristic value 1 day curing strength >1000psi 7 days curing strength >3000psi 28 days curing strength >4000psi Table 5. Composition C containing saline Table 6. Composition D Table 7. Properties of Composition D characteristic value 1 day curing strength >1000psi 7 days curing strength >3000psi 28 days curing strength >4000psi Table 8. Composition E Note: (A) + (B) = 100% Table 9. Properties of Composition E characteristic value 1 day curing strength -- 7 days curing strength >3000psi 28 days curing strength >4000psi Table 10. Composition F Note: (A) + (B) = 100% Table 11. Properties of Composition F characteristic value 1 day curing strength -- 7 days curing strength - 28 days curing strength >4000psi Table 12. Composition G Note: (A) + (B) = 100% Table 13. Properties of Composition G characteristic value 1 day curing strength -- 7 days curing strength >3000psi 28 days curing strength >3000psi Table 14. Composition H Table 15. Properties of Composition H characteristic value 1 day curing strength >3000psi 7 days curing strength >4000psi 28 days curing strength >5000psi
[0210] Comparative strength. After curing for 3, 7, 14, 28, 56, 90 and 180 days on a 50 mm cube sample, the compressive strength of concrete was measured using a digital compressor according to ASTM C109 [ASTM C109-10, Standard Test Method for Compressive Strength of Hydraulic Cement Mortar (Using 2 inches or [50-mm] cube samples), ASTM International, West Conshohocken, Pa., 2010]. After each curing period, the sample was taken out of the oven and allowed to cool before testing. Three replicate samples were prepared for each curing period and tested under compression. The average value of the three readings was reported.
[0211] As contemplated herein, once combined with water and allowed to cure, the mixture has a 1-day strength of at least 1000 psi, 1500 psi, 2000 psi, 2500 psi, 3000 psi, 3500 psi, 4000 psi, 4500 psi, 5000 psi, 5500 psi, 6000 psi, 6500 psi, 7000 psi, 7500 psi, 8000 psi, 8500 psi, 9000 psi or greater, including any value or sub-range within the recited range, including the endpoints. In some embodiments, once combined with water and allowed to cure, the mixture has a 7-day strength of at least 1000 psi, 1500 psi, 2000 psi, 2500 psi, 3000 psi, 3500 psi, 4000 psi, 4500 psi, 5000 psi, 5500 psi, 6000 psi, 6500 psi, 7000 psi, including any value or sub-range within the recited range, including endpoints. In some embodiments, once combined with water and allowed to cure, the mixture has a 28-day strength of at least 1000 psi, 1500 psi, 2000 psi, 2500 psi, 3000 psi, 3500 psi, 4000 psi, 4500 psi, 5000 psi, 5500 psi, 6000 psi, 6500 psi, 7000 psi, including any value or sub-range within the recited range, including endpoints.
[0212] Flexural Strength. Prismatic specimens measuring 50x50x200 mm were prepared to determine the flexural strength of concrete using a third point load according to ASTM C78 [ASTM C1437-10, Standard Specification for Fly Ash and Raw or Calcined Natural Pozzolans for Use in Concrete, ASTM International, West Conshohocken, Pa., 2010; ASTM C78-10, Standard Test Method for Flexural Strength of Concrete (Using Simple Beam with Third Point Loading), ASTM International, West Conshohocken, Pa., 2010]. The flexural strength of concrete was determined at 28 days and 90 days of curing. Triplicate specimens of each mixture within a specific curing period were prepared and tested. The average of the three readings was reported.
[0213] Modulus of elasticity. The modulus of elasticity of concrete was measured on cylindrical concrete specimens of 75 mm diameter and 150 mm height. The test was conducted according to ASTM C 469 [ASTM C496-10, Standard Test Method for Splitting Tensile Strength of Cylindrical Concrete Specimens, ASTM International, West Conshohocken, Pa., 2010]. The modulus of elasticity was measured after 28 days and 90 days of curing. Environmental impact
[0214] The present application encompasses the production of a residential structure made of residential materials that meets current residential shortages while generating carbon credits. In embodiments, the residential structure is made of cementitious materials with negative carbon dioxide emissions. In other embodiments, the cementitious materials with negative carbon dioxide emissions are cementitious masonry units (masonry units) manufactured by the methods described herein. The production of cementitious masonry units (building blocks) provided herein absorbs carbon dioxide and has reduced the output of carbon dioxide based on the manufacturing method. In some embodiments, the production does not require fresh water.
[0215] Each masonry unit is 0.0076m 3 volume of cementitious material, which weighed 38.5 pounds (17.5 kg). After testing, this negative CO2 emitting cementitious material absorbed 32 kg CO2 / mt / year (mt means metric tons). Therefore, for each block over a 20-year period: 17.5kg x 0.001 metric ton / kg x 32kg CO2 / metric ton / year x 20 years = 11.2kg CO2 / block in 20 years
[0216] Each block also produces less CO2 than conventional concrete and other cement products: 0.0076m 3 x 405kg CO2 / m 3 = Each block avoids 3.08kg CO2
[0217] Therefore, the total carbon credit (avoidance of 11.2 kg CO2 / block + removal of 3.1 kg CO2 / block) is 14.3 kg (31.5 lbs) CO2 / block. Note: 405 kg CO2 / m 3Based on DuPont EPD High Test CMU900003403, issued on August 31, 2021, valid until August 31, 2026 (www.basalite-cmu.com / _files / ugd / 31fd52_c399e811721a4fa4b9fe9cf4bd91c2e6.pdf)
[0218] Next, the above calculation is converted into an application calculation in which cementitious masonry blocks are combined with mortar (or filler). Carbon removal, 22.6 kg (49.8 lbs): 11.2 kg CO2 / block (calculated above) + 11.4 kg (mortar / filler) 11.2kg CO2 / block + [Mortar / Filling] 11.2kg CO2 / block x 1.02kg mortar / kg block = 22.6kg CO2 Carbon avoidance, 6.22kg (13.7 lbs): 3.08kg (based on above calculation) + 3.14kg (mortar) 3.08kg (block) + 3.08kg CO2 / block x 1.02kg mortar / kg block = 6.22kg CO2
[0219] The total carbon credit (22.6 kg CO2 removed + 6.22 kg CO2 avoided) is 28.8 kg CO2 (63.5 lbs) per block.
[0220] The environmental impact of the materials covered herein extends to the consumption of fresh water, wherein the compositions of the present application do not use fresh water or treated water in the manufacturing process. According to USEPA (https: / / www.epa.gov / indoor-air-quality-iaq / introduction-indoor-air-quality), the carbon dioxide absorption equivalent of a medium-grown conifer tree allowed to grow for 10 years is 23.2 pounds of CO2 (10.5 kg). Therefore, referring to the above calculation, each cementitious masonry unit removes 11.2 kg of CO2, which is approximately equivalent to 1 tree. For each cementitious masonry unit applied, referring to the above calculation, 20.4 kg of CO2 is removed, which is equivalent to two trees.
[0221] In embodiments of the compositions provided herein, the cementitious masonry units are used to construct a house. In embodiments, the house size is 1250 feet 2 Each house uses 3,000 units of applied cementitious masonry. In addition to the mortar and fill materials for the applied masonry units, each home also includes 62.9 m2 of concrete in the foundation, slab, porch, roof tiles, driveway and sidewalk.3 Cementitious material. The density of the material used is 1505kg / m 3 (or 94 lbs / ft 3 ), absorbing 32kg CO2 / metric ton / year. In embodiments, the present application avoids the need for additional materials, such as drywall, insulation, asphalt roofing, and paint. Carbon removal for 1 house (1250 ft 2 )(116.1m 2 ) Blocks used: 22.6kg CO2 x 3000 blocks / house = 67800kg CO2 or 67.8 metric tons CO2 (credits) Foundation, slab, porch, roof tiles, driveway and sidewalk: 62.9m 3 x 1505kg / m 3 x 0.001 metric tonne / kg x 32kg CO2 / metric tonne / year x 20 years = 60,585kg CO2 or 60.6 metric tonnes of CO2 (credit) 67.8 metric tons of CO2 (credits) + 60.6 metric tons of CO2 (credits) = 128.4 metric tons of CO2 (credits) Carbon avoidance for 1 house (1250 ft 2 )(116.1m 2 ) Blocks used: 6.24kg CO2 x 3000 blocks / house = 18720kg CO2 or 18.7 metric tons CO2 (credits) Foundation, slab, porch, roof tiles, driveway and sidewalk: 62.9m 3 x 405kg CO2 / m 3 = 25475 kg CO2 or 25.5 metric tons CO2 (credit) 18.7 metric tons of CO2 (credits) + 25.5 metric tons of CO2 (credits) = 44.2 metric tons of CO2 (credits) Additional avoidance during construction = 10 credits Total carbon credits (removed + avoided) 128.4 metric tons CO2 + 44.2 metric tons CO2 + 10 metric tons CO2 = 182.6 metric tons or credits / house
[0222] In embodiments of the compositions provided herein, the negative carbon dioxide emitting cementitious material is a paving material. In embodiments, the plurality of paving materials covers 100,000 m 2 In the embodiment, the paving material is 3 inches thick (0.2286 m). Therefore, for 100,000 m 2 of surface area, paving material contains 22860m3 The density of the cementitious material with negative carbon dioxide emissions is 1505 kg / m 3 , 22860m 3 (Volume of paving material) x 1505kg / m 3 (Density) x 0.001 metric tonnes / kg provides 34,404 metric tonnes of material for use in paving materials. 100000m 2 Carbon Removal from Paving Materials 34,404 metric tons x 32 kg CO2 / metric ton / year x 20 years x 0.001 metric ton / kg = 22,018 metric tons CO2 (credits) 100000m 2 Carbon Avoidance in Paving Materials 22860m 3 x 405kg CO2 / m 3 = 9,258,300 kg or 9,258 metric tons of CO2 credit Total carbon credits (avoidance + removal) = 22,018 metric tons + 9,258 metric tons = 31,276 credits / 100,000m 2 Paving materials
[0223] Although the foregoing embodiments have been described in considerable detail by way of illustration and example for clarity of understanding, it will be appreciated by those skilled in the art that certain variations and modifications may be practiced within the scope of the appended claims. In addition, each reference provided herein is incorporated by reference in its entirety to the same extent as if each reference were individually incorporated by reference. In the event of a conflict between the present application and the references provided herein, the present application shall prevail.
Claims
1. An artificial stone-like material solidified by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) Natural volcanic ash; (b) artificial volcanic ash; (c) aqueous solutions; (d) one or more accelerators; and, (e) at least one aggregate, optionally selected.
2. The artificial stone-like material of claim 1, wherein the accelerator comprises one or more of nitrate, sulfate, sodium, chloride and phosphate.
3. The artificial stone-like material of claim 1 or 2, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone and combinations thereof.
4. The artificial stone-like material according to any one of claims 1 to 3, wherein the poured cementitious mixture further comprises an accelerating admixture selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride.
5. The artificial stone-like material according to any one of claims 1 to 4, wherein the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay, shale, wollastonite, opal shale, diatomaceous earth, olivine and combinations thereof.
6. The artificial stone-like material according to any one of claims 1 to 5, wherein the artificial pozzolan is selected from metakaolin, fly ash, silica fume, ground glass (e.g., ground waste glass), slag (e.g., ground granulated blast furnace slag, blast furnace slag, steelmaking furnace slag, basic oxygen furnace slag, electric arc furnace slag, ladle slag, copper slag, steel slag, iron slag, lead slag, nickel slag, zinc slag, aluminum slag or slag of other metals), organic combustion residue (e.g., rice husk ash / ricehull ash), expanded clay, expanded shale, calcined clay and combinations thereof.
7. The artificial stone-like material according to any one of claims 1 to 6, wherein the artificial stone-like material is solidified by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
8. The artificial stone-like material according to any one of claims 1 to 7, wherein the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 33 wt.% to about 300 wt.%.
9. The artificial stone-like material according to any one of claims 1 to 8, wherein the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 50 wt.% to about 200 wt.%.
10. The artificial stone-like material according to any one of claims 1 to 9, wherein the amount of natural pozzolan present relative to the amount of artificial pozzolan ranges from about 85 wt.% to about 115 wt.%.
11. The artificial stone-like material according to any one of claims 1 to 10, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of artificial pozzolan.
12. The artificial stone-like material according to any one of claims 1 to 11, wherein the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of artificial pozzolan.
13. The artificial stone-like material according to any one of claims 1 to 12, wherein the amount of sulfate present is in the range of about 20 wt.% to about 50% wt.% relative to the amount of artificial pozzolan.
14. The artificial stone-like material according to any one of claims 1 to 13, wherein the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of artificial pozzolan.
15. The artificial stone-like material according to any one of claims 1 to 14, wherein the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of artificial pozzolan.
16. The artificial stone-like material according to any one of claims 1 to 15, further comprising MgO and / or Mg(OH)2.
17. An artificial stone-like material that is set by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) volcanic ash; (b) MgO; (c) aqueous solutions; (d) one or more accelerators; and, (e) at least one aggregate, optionally selected.
18. The artificial stone-like material of claim 17, wherein the accelerator comprises one or more of nitrate, sulfate, sodium, chloride and phosphate.
19. The artificial stone-like material of claim 17 or 18, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
20. The artificial stone-like material according to any one of claims 17 to 19, wherein the poured cementitious mixture further comprises an accelerating admixture selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride.
21. The artificial stone-like material according to any one of claims 17 to 20, wherein the pozzolan is selected from the group consisting of artificial pozzolan, natural pozzolan and combinations thereof.
22. The artificial stone-like material of any one of claims 17 to 21, wherein the artificial stone-like material is set by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
23. The artificial stone-like material of any one of claims 17 to 22, wherein the amount of pozzolan present relative to the amount of MgO ranges from about 33 wt.% to about 300 wt.%.
24. The artificial stone-like material of any one of claims 17 to 23, wherein the amount of pozzolan present relative to the amount of MgO ranges from about 50 wt.% to about 200 wt.%.
25. The artificial stone-like material of any one of claims 17 to 24, wherein the amount of pozzolan present relative to the amount of MgO ranges from about 85 wt.% to about 115 wt.%.
26. The artificial stone-like material of any one of claims 17 to 25, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of pozzolan.
27. The artificial stone-like material of any one of claims 17 to 26, wherein the amount of sulfate present relative to the amount of pozzolan ranges from about 0.1 wt.% to about 90 wt.%.
28. The artificial stone-like material of any one of claims 17 to 27, wherein the amount of sulfate present relative to the amount of pozzolan ranges from about 20 wt.% to about 50% wt.%.
29. The artificial stone-like material of any one of claims 17 to 28, wherein the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of pozzolan.
30. The artificial stone-like material of any one of claims 17 to 29, wherein the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of pozzolan.
31. An artificial stone-like material that is set by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) volcanic ash; (b)Mg(OH)2; (c) aqueous solutions; (d) one or more accelerators; and, (e) at least one aggregate, optionally selected.
32. The artificial stone-like material of claim 31, wherein the accelerator comprises one or more of nitrate, sulfate, sodium, chloride and phosphate.
33. The artificial stone-like material of claim 31 or 32, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
34. The artificial stone-like material of any one of claims 31 to 33, wherein the poured cementitious mixture further comprises an accelerating admixture selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride.
35. The artificial stone-like material according to any one of claims 31 to 34, wherein the pozzolan is selected from the group consisting of artificial pozzolan, natural pozzolan and combinations thereof.
36. The artificial stone-like material of any one of claims 31 to 35, wherein the artificial stone-like material is set by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
37. The artificial stone-like material of any one of claims 31 to 36, wherein the amount of pozzolan present relative to the amount of Mg(OH)2 ranges from about 33 wt.% to about 300 wt.%.
38. The artificial stone-like material of any one of claims 31 to 37, wherein the amount of pozzolan present relative to the amount of Mg(OH)2 ranges from about 50 wt.% to about 200 wt.%.
39. The artificial stone-like material of any one of claims 31 to 38, wherein the amount of pozzolan present relative to the amount of Mg(OH)2 ranges from about 85 wt.% to about 115 wt.%.
40. The artificial stone-like material of any one of claims 31 to 39, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of pozzolan.
41. The artificial stone-like material of any one of claims 31 to 40, wherein the amount of sulfate present relative to the amount of pozzolan ranges from about 0.1 wt.% to about 90 wt.%.
42. The artificial stone-like material of any one of claims 31 to 41, wherein the amount of sulfate present relative to the amount of pozzolan ranges from about 20 wt.% to about 50% wt.%.
43. The artificial stone-like material of any one of claims 31 to 42, wherein the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of pozzolan.
44. The artificial stone-like material of any one of claims 31 to 43, wherein the amount of phosphate present relative to the amount of pozzolan ranges from about 0.1 wt.% to about 20 wt.%.
45. An artificial stone-like material that is set by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) Natural volcanic ash; (b) grinding granulated blast furnace slag; and (c) an aqueous solution comprising one or more promoters.
46. The artificial stone-like material of claim 45, wherein the accelerator comprises one or more of nitrate, sulfate, sodium, chloride and phosphate.
47. The artificial stone-like material of claim 45 or 46, wherein the poured cementitious mixture further comprises at least one aggregate.
48. The artificial stone-like material of claim 47, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
49. The artificial stone-like material of any one of claims 45 to 48, wherein the poured cementitious mixture further comprises an accelerating admixture selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride.
50. The artificial stone-like material of any one of claims 45 to 49, wherein the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay, sedimentary shale, calcined clay, rice husk ash, diatomaceous earth, metakaolin, olivine and combinations thereof.
51. The artificial stone-like material according to any one of claims 45 to 50, wherein the natural volcanic ash is basalt.
52. An artificial stone-like material that is set by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) Natural volcanic ash; (b) grinding granulated blast furnace slag; (c) an aqueous solution comprising one or more accelerators; and (d) at least one aggregate.
53. The artificial stone-like material of claim 52, wherein the accelerator comprises one or more of nitrates, sulfates, sodium, chlorides and phosphates.
54. The artificial stone-like material of claim 52 or 53, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
55. The artificial stone-like material of any one of claims 52 to 54, wherein the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay and shale, calcined clay, rice husk ash, diatomaceous earth, metakaolin, olivine and combinations thereof.
56. The artificial stone-like material according to any one of claims 52 to 55, wherein the natural volcanic ash is basalt.
57. The artificial stone-like material of any one of claims 45 to 56, wherein the artificial stone-like material is set by pouring the cementitious mixture and then applying a curing technique to the poured cementitious mixture.
58. The artificial stone-like material of any one of claims 45 to 57, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
59. The artificial stone-like material of any one of claims 45 to 58, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 33 wt.% to about 300 wt.%.
60. The artificial stone-like material of any one of claims 45 to 59, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 50 wt.% to about 200 wt.%.
61. The artificial stone-like material of any one of claims 45 to 60, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 85 wt.% to about 115 wt.%.
62. The artificial stone-like material of any one of claims 45 to 61, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of ground granulated blast furnace slag.
63. The artificial stone-like material of any one of claims 45 to 62, wherein the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of ground granulated blast furnace slag.
64. The artificial stone-like material as claimed in any one of claims 45 to 63, wherein the amount of sulfate present is in the range of about 20 wt.% to about 50% wt.% relative to the amount of ground granulated blast furnace slag.
65. The artificial stone-like material as claimed in any one of claims 45 to 64, wherein the amount of chloride present is in the range of about 0.1 wt.% to about 12 wt.% relative to the amount of ground granulated blast furnace slag.
66. The artificial stone-like material of any one of claims 45 to 65, wherein the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of ground granulated blast furnace slag.
67. The artificial stone-like material of any one of claims 45 to 66, wherein the cast cementitious mixture further comprises MgO and / or Mg(OH)2.
68. The artificial stone-like material of any one of claims 45 to 67, wherein the cast cementitious mixture further comprises CaO.
69. An artificial stone-like material formed from a poured cementitious mixture and configured to absorb and retain carbon dioxide, the poured cementitious mixture comprising: (a) Natural volcanic ash; (b) grinding granulated blast furnace slag; (c) an aqueous solution comprising one or more accelerators; and (d) at least one aggregate optionally selected.
70. The artificial stone-like material of claim 69, wherein the poured cementitious mixture absorbs and retains carbon dioxide for a period of time as it cures and hardens.
71. The artificial stone-like material of claim 69 or 70, wherein the accelerator comprises one or more of nitrate, sulfate, sodium, chloride and phosphate.
72. The artificial stone-like material of any one of claims 69 to 71, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone and combinations thereof.
73. The artificial stone-like material of any one of claims 69 to 72, wherein the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay and shale, calcined clay, rice husk ash, diatomaceous earth, metakaolin, olivine and combinations thereof.
74. The artificial stone-like material of any one of claims 69 to 73, wherein the natural volcanic ash is basalt.
75. The artificial stone-like material of any one of claims 69 to 74, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 33 wt.% to about 300 wt.%.
76. The artificial stone-like material of any one of claims 69 to 75, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 50 wt.% to about 200 wt.%.
77. The artificial stone-like material of any one of claims 69 to 76, wherein the amount of natural pozzolan present relative to the amount of ground granulated blast furnace slag ranges from about 85 wt.% to about 115 wt.%.
78. The artificial stone-like material as claimed in any one of claims 69 to 77, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of ground granulated blast furnace.
79. The artificial stone-like material as claimed in any one of claims 69 to 77, wherein the amount of sulfate present is in the range of about 0.1 wt.% to about 90 wt.% relative to the amount of ground granulated blast furnace.
80. The artificial stone-like material of any one of claims 69 to 77, wherein the amount of sulfate present is in the range of about 20 wt.% to about 50 wt.% relative to the amount of ground granulated blast furnace slag.
81. The artificial stone-like material as claimed in any one of claims 69 to 77, wherein the amount of chloride present is in the range of about 0.1 wt. % to about 12 wt. % relative to the amount of ground granulated blast furnace slag.
82. The artificial stone-like material of any one of claims 69 to 77, wherein the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of ground granulated blast furnace slag.
83. The artificial stone-like material of any one of claims 69 to 82, wherein the poured concrete mix absorbs and retains at least 5% by weight of the carbon dioxide in the artificial stone-like material over a period of 15 years.
84. A method for producing an artificial stone-like material with negative carbon dioxide emissions, the method comprising: (a) mixing natural pozzolan with ground granulated blast furnace slag in an aqueous solution containing one or more accelerators to form a cementitious mixture; (b) pouring the cementitious mixture into a structural component mold to form a poured cementitious mixture; and then, (c) curing the cementitious concrete mixture from step (b) in the structural mould to form a negative carbon dioxide emitting artificial stone-like material.
85. The manufacturing method of claim 84, further comprising adding a water-repellent silane or an oil-repellent silane to the cementitious mixture of step (a).
86. The method of manufacture of claim 84 or 85, wherein the amount of natural pozzolan present is in the range of about 33 wt.% to about 300 wt.% relative to the amount of ground granulated blast furnace slag.
87. The manufacturing method of any one of claims 84 to 86, wherein the amount of natural pozzolan present is in the range of about 50 wt.% to about 200 wt.% relative to the amount of ground granulated blast furnace slag.
88. The method of manufacture of any one of claims 84 to 87, wherein the amount of natural pozzolan present is in the range of about 85 wt.% to about 115 wt.% relative to the amount of ground granulated blast furnace slag.
89. The method of manufacture of any one of claims 84 to 88, wherein the amount of nitrate present is in the range of about 2 wt.% to about 30 wt.% relative to the amount of ground granulated blast furnace slag.
90. The method of manufacture of any one of claims 84 to 89, wherein the amount of sulfate present is in the range of about 0.1 wt. % to about 90 wt. % relative to the amount of ground granulated blast furnace slag.
91. The method of manufacture of any one of claims 84 to 90, wherein the amount of sulfate present is in the range of about 20 wt. % to about 50 wt. % relative to the amount of ground granulated blast furnace slag.
92. The method of manufacture as claimed in any one of claims 84 to 91, wherein the amount of chloride present is in the range of about 0.1 wt. % to about 12 wt. % relative to the amount of ground granulated blast furnace slag.
93. The manufacturing method of any one of claims 84 to 92, wherein the amount of phosphate present is in the range of about 0.1 wt.% to about 20 wt.% relative to the amount of ground granulated blast furnace slag.
94. A method for reducing carbon emissions, the method comprising: (a) mixing natural pozzolan, artificial pozzolan, aqueous solution and one or more accelerators to form a cementitious mixture; (b) pouring the cementitious mixture to form a poured cementitious mixture; (c) curing the poured cementitious mixture from step (b) to form a negative carbon dioxide emitting cementitious material; This results in a negative CO2 emitting cementitious material which absorbs carbon dioxide and prevents its emission.
95. The method of claim 94, wherein the carbon emissions reduction consists of the amount of carbon dioxide absorbed and the amount of carbon dioxide prevented from being emitted.
96. The method of claim 94, wherein the negative CO2 emitting cementitious material is a cementitious masonry unit.
97. The method of claim 96, wherein the cementitious masonry unit absorbs 11.2 kg CO2 over a 20 year period and emits 3.08 kg CO2 per cementitious masonry unit.
98. The method of claim 97, wherein the plurality of cementitious masonry units are combined with a fill or mortar material to form a plurality of cementitious masonry units having a length of at least 1250 feet. 2 house structure.
99. The method of claim 98, wherein the housing structure absorbs at least 120 metric tons of CO2 and prevents the emission of at least 40 metric tons of CO2.
100. The method of claim 94, wherein the negative CO2 emitting cementitious material is a paving material.
101. The method of claim 100, wherein the plurality of paving materials have a thickness of 100,000 m 2 surface area.
102. The method of claim 101, wherein the plurality of paving materials absorb at least 20,000 metric tons of CO2 and prevent the emission of at least 9,000 metric tons of CO2.
103. The method of any one of claims 94 to 102, wherein the negative carbon dioxide emitting cementitious material comprises an artificial stone-like material as claimed in any one of claims 1 to 83, or an artificial stone-like material manufactured by the method of any one of claims 84 to 93.
104. An artificial stone-like material that solidifies by pouring a cementitious mixture, the poured cementitious mixture comprising: (a) Natural volcanic ash; (b) grinding granulated blast furnace slag; and (c) an aqueous solution; and, (d) one or more promoters.
105. The artificial stone-like material of claim 104, wherein the accelerator comprises one or more of nitrates, sulfates, sodium, chlorides and phosphates.
106. The artificial stone-like material of claim 104 or 105, wherein the poured cementitious mixture further comprises at least one aggregate.
107. The artificial stone-like material of claim 106, wherein the at least one aggregate is selected from the group consisting of sand, gravel, lightweight aggregate, crushed stone, and combinations thereof.
108. The artificial stone-like material of any one of claims 104 to 107, wherein the poured cementitious mixture further comprises an accelerating admixture selected from triethanolamine, calcium formate, silica fume, finely powdered silica gel and calcium chloride.
109. The artificial stone-like material of any one of claims 104 to 108, wherein the natural volcanic ash is selected from rhyolite, obsidian, pitchstone, pumice, basalt, andesite, volcanic ash, sedimentary clay, sedimentary shale, calcined clay, rice husk ash, diatomaceous earth, metakaolin, olivine and combinations thereof.
110. The artificial stone-like material according to any one of claims 104 to 109, wherein the natural volcanic ash is basalt.
